Synergistic co-immobilization of magnetite and powdered activated carbon nanocomposites for enhanced dark fermentative biohydrogen production and reusability - Sandhya Sompura; Eunjin Kim; Yerim Lee; Eunseo Cho; Young-Bo Sim; Sang-Hyoun Kim; Ju-Hyeong Jung (Fuel, 2026)

From lignin to lipids, and beyond: A holistic perspective on genetic tools, lignin and fatty acid metabolism, strain engineering, and bioprocess optimization in Rhodococcus opacus PD630 and Rhodococcus jostii RHA1 - Sandhya Sekhar; Senthilkumar Sivaprakasam; Selvaraju Narayanasamy (Biomass and Bioenergy, 2026)

Utilization of MADS-Box genes for agricultural advancement: current insights and future prospects - Anupam Tripathi; Kiran Vishwakarma; Sandhya Tripathi; Jyoti Singh Jadaun; Amrit Kumar Nayak (Molecular Biology Reports, 2026)

Identification of candidate genes governing key metabolic pathways in fenugreek (Trigonella spp.) through integrated transcriptomic and metabolomic analysis - Sheel Yadav; Wanchha Maurya; Ratna Kumari; Sandhya Sharma; Parimalan Rangan; Ambika Baldev Gaikwad (Functional & Integrative Genomics, 2026)

Pest-induced damage detection in corn leaves using improved Faster R-CNN - Suresh Timilsina; Sandhya Sharma; Kazuhiko Sato; Yoshifumi Okada; Shinya Watanabe; Satoshi Kondo (Computers and Electronics in Agriculture, 2026)

Phylogenetic diversity and plant growth-promoting traits of mangrove root-associated bacterial communities: Implications for bioinoculant development - Helen Agnes; S.V. Sandhya; R. Amal; Anoop Babu; Darwin Ramteke (Regional Studies in Marine Science, 2026)

Turning RuBisCO-enriched snap pea protein concentrates into function: A novel plant protein for fat-free whipped cream alternatives - Qinghao Ning; Jordy Kim Ung Ling; Jia Yee Wu; Tamilvendan Manavalan; Gomathy Sandhya Subramanian; Nurhidayah Basri; Yin Win Khin; Yoganathan Kanagasundaram; Jayantha Gunaratne; Maria N. Antipina; Siew Bee Ng (Food Hydrocolloids, 2026)

Quinone-fused diazepine π-conjugated carbon black: A chemically induced, topological-defect like engineered platform for ultrastable redox activity and ultrasensitive electrocatalytic sensing of ascorbic acid - Kumar Sandhya; Sugumar Monisha; Rajan Reshma; Krishnan Ashokkumar; K. Sriraghavan; Annamalai Senthil Kumar (Chemical Engineering Journal, 2026)

Microphysical evolution of fog: Transition from haze to fog in Delhi - Prasanna Lonkar; Sandhya Jose; Sandeep Wagh; Pooja Pawar; Sumit Kumar; Suresh Gosavi; Akash S. Vispute; Sachin D. Ghude (Atmospheric Environment, 2026)

Arthropod–plant–pathogen dynamics: integrated characterization of sugarcane crown mealybug (Phenacoccus saccharifolii Green, 1908) infestation and its associated Fusarium species complex - Sandhya Namadara; Madesh Kamalakannan; Kannan Malaichamy; Anandham Rangasamy; Prakash Kolanchi; Pragadeesh Ayyamuthu Rajarathinam Uma; Nanthitha Ashok; Abishagu Arulanandar; Senthilkumar Murugaiyan (Journal of Plant Diseases and Protection, 2026)

Efficacy of seed priming through different plant extracts on seed germination of Naga-King Chilli (Capsicum chinense Jacq.) - Kime Tare; Rajesh Kumar; Amrit Lamichaney; Tshering Lhamu Sherpa; Koushik Baruah; Lomash Sharma; Sandhya Lamichaney (Acta Physiologiae Plantarum, 2026)

Therapeutic Medication Errors in the Non-Healthcare Facility Setting Associated with Hospital Admission, 2000–2024 - Srija Nuguri; Sandhya Kistamgari; Hannah L. Hays; Natalie I. Rine; Nichole L. Michaels; Motao Zhu; Gary A. Smith (Journal of Medical Toxicology, 2026)
Introduction This study investigated the characteristics and trends of therapeutic medication errors reported to United States (US) poison centers that occurred in a non-healthcare facility setting and were associated with hospital admission. Methods Using a retrospective cohort design, National Poison Data System data from 2000 to 2024 were analyzed. US Census Bureau data were used to calculate population-based rates. Results There were 115,071 therapeutic medication errors that occurred in a non-healthcare facility setting and were associated with hospital admission reported to US poison centers from 2000 to 2024. Most involved females (55.5%), individuals > 49 years old (56.9%), a single substance (71.5%), or occurred in a residence (96.0%). In addition, 39.0% were admitted to a critical care unit and 53.3% were associated with a serious medical outcome, including moderate effects (45.4%), major effects (7.2%), or death (0.7%, n = 745). Cardiovascular drugs (24.7%), analgesics (18.2%), and antidepressants (11.3%) were most commonly involved. The overall hospitalized therapeutic medication error rate per one million US population increased by 196.9% from 7.06 in 2000 to 20.97 in 2024; the rate was highest among adults > 69 years old, females, and errors involving cardiovascular drugs. Of the 115,009 exposures in which at least one therapeutic medication error scenario was reported, the most common scenarios were “other incorrect dose” (23.6%), “wrong medication taken/given” (16.7%), and “inadvertently took/given medication twice” (13.9%). Conclusions These study findings highlight opportunities to strengthen prevention efforts targeting therapeutic medication errors, particularly among older adults and individuals using cardiovascular medications, which could meaningfully decrease associated morbidity, mortality, and healthcare costs.

Electrospun nanofiber-based platforms for mycotoxins sensing: Recent advances and future directions - Vanish Kumar; Sandhya Ruhal; Ki-Hyun Kim (Food Chemistry, 2026)

Impact of advanced cloud microphysics schemes for the Kerala flood events in 2018 and 2019 using the NCMRWF regional model - Rose Raphel; A. Jayakumar; T.J. Anurose; Saji Mohandas; Greeshma M. Mohan; M. Sandhya; Anumeha Dube; Donali Gogoi; V.S. Prasad; Claudio Sanchez (Atmospheric Research, 2026)

Omics-Mediated Insights on Alternative Splicing in the Abiotic Stress Response - Preeti Sharma; Jayanti Tokas; Manju Rani; Shivangi Bishnoi; Sandhya Sharma (Plant Molecular Biology Reporter, 2026)

Comparative Seasonal Proteome Profiling of the Liverwort Plagiochasma appendiculatum Reveals Molecular Strategies of Acclimation in its Natural Habitat - Vishal Kumar Jha; Akanksha Srivastava; Sandhya Yadav; Suvajit Basu; Subhankar Biswas; Kritika Tripathi; Neha Chaurasia; Sushil Kumar Singh; Vaibhav Srivastava; Yogesh Mishra (Plant Molecular Biology Reporter, 2026)

Screening and optimisation of crude exopolysaccharide production by marine Brevibacterium sp. JAB08 isolated from the jellyfish Chrysaora sp. from the coastal waters of Goa - Balaji Vaishnavi; R. Amal; Biraja Kumar Sahu; S. V. Sandhya (Antonie van Leeuwenhoek, 2026)

Elevated CO2 and temperature reshape soybean chemistry and drive physiological and life-history trade-offs in the beet webworm Loxostege sticticalis - Jingxian Zhou; Shuqi Ren; Pin Li; Sandhya Samarasinghe; Xingfu Jiang; Guijun Wan; Fajun Chen (Journal of Pest Science, 2026)

Occurrence, quantification, and characterization of microplastics in sewage sludge from a university wastewater treatment system - Sandhya Kumari Gupta; Pallavi Vadla; Sankar Ganesh Palani (Environmental Monitoring and Assessment, 2026)

ARF Gene Family: Expression Dynamics, Signalling, and Importance in Seed Development - Kumari Arpita; Sandhya Sharma; Anshika Tyagi; Arvind Yadav; Sandeep Kumar; Rupesh Deshmukh; Robert M Stupar; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Phase-Resolved Impacts of Daytime, Nighttime, and Compound Heatwaves on Urban Air Quality in Delhi - Renu Masiwal; Dilip Ganguly; Sandhya Jose; Ashima Sharma; Ravi K. Kunchala; Sagnik Dey (Sustainable Cities and Society, 2026)

Enhanced glyphosate biodegradation by heavy metal-tolerant microbial consortium QLBS in co-contaminated environment: Kinetics and metabolic pathways - Zeren Li; Mengyi Chen; Ziye Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Haoran Song; Huijie Zhou; Zhenyu Zhang; Bin Liang; Sandhya Mishra; Mohamed A. Ghorab; et al. (Journal of Cleaner Production, 2026)

A Lightweight and Interpretable Recurrent Vision Transformer for Robust Potato Blight Classification - Prakash Sandhya; B Venkataramana (Potato Research, 2026)

Integrative transcriptome and long non-coding RNA analysis to decipher the molecular basis of cleistogamy in pigeonpea (Cajanus cajan (L) Millsp) - Palak Gupta; Harsha Srivastava; Kuldeep Kumar; Kishor U. Tribhuvan; Tanvi Kaila; Swati Saxena; Kumar Durgesh; Sandhya Sharma; Kishor Gaikwad (Planta, 2026)

ABA treatment on AtAVT6D-overexpressing Arabidopsis thaliana plants results in perturbation of ROS pathway genes - Arti Narendra Karamchandani; Sandhya Mehrotra; Rajesh Mehrotra (Physiology and Molecular Biology of Plants, 2026)

A stability indicating analytical method development and validation of drug Tafamidis using RP-HPLC - Sandhya Shinde; Moreshwar Mahajan (Journal of Pharmaceutical Innovation, 2026)

Development of in vitro germination and cryopreservation protocols of pollen in wild Lathyrus species to overcome longevity and asynchronous flowering constraints - Rinky Resma Panda; Padmavati G. Gore; Aishmita Gantait; Esha Singh; Mahesh Rao; S. Rajkumar; Shiv Kumar; Kuldeep Tripathi; Sandhya Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Stability and climate resilience of garlic genotypes under organic conditions of Sikkim Himalaya - Lomash Sharma; Rajesh Kumar; Kime Tare; Sandhya Lamichaney (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Development of a double-pharmacophore workflow for screening subtype-selective M3 muscarinic acetylcholine receptor antagonists - Sirat Kaur Gill; Sandhya Chahal; Shyam Sundar Sarkar; Tara Yadava; Jayant Sindhu; Badri N. Acharya (Molecular Diversity, 2026)

Towards water-resilient cities: exploring rain gardens as urban flood mitigation in Delhi - Arup Babu; Apoorva Singh; Arkadip Mallik; Sandhya Rao; Ashvani Kumar Gosain; C T Dhanya (Journal of Earth System Science, 2026)

Resistance of pink bollworm Pectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae) to Cry1Ac and Cry2Ab toxins in major cotton-growing regions of South India - Naduvalakeri Maruti; N. V.V. Durga Prasad; V. Chinna Babu Naik; C. Sandhya Rani; Suresh R. Jambagi (International Journal of Tropical Insect Science, 2026)

Improving lightning representation in global model through convective cloud based Price and Rind 1992 scheme - M. Sandhya; Greeshma M. Mohan; Saji Mohandas; A. Jayakumar; T.J. Anurose; V.S. Prasad (Science of The Total Environment, 2026)

Corrigendum to “Artificial intelligence-based solar radiation forecasting for efficient use of renewable power plants” [J. Atmos. Sol. Terr. Phys., 282 (2026), 106786] - Vishal Sorathiya; Sanjeev Kumar Mandal; Sandhya Umrao; Keerti Rai; Pavan Chaudhary; Sumitra Padmanabhan (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Integrative metabolomics and molecular interactions suggest neuroendocrine and detoxification targets for Simarouba glauca against Spodoptera frugiperda - Prakash Kolanchi; A.R.U. Pragadeesh; Namadara Sandhya; Dineshkumar Selvaraj; Komala Gudla (Journal of Asia-Pacific Entomology, 2026)

An explainable AI framework for prioritising EPC D-G retrofits across England and Wales through emission-driven dwelling typologies and spatial delivery clusters - Zhihao Zhang; Sahar Mirzaie; Sandhya Patidar (Energy and Buildings, 2026)

Enhancement of physical and electrochemical activity of polyvinyl alcohol/chitosan/bentonite based membrane through sulfonation for the bioelectricity generation in microbial fuel cell - Sandhya; Nethavath Prashanth; Banoth Vamshikrishna; Astha; Ganesh Swain (Bioresource Technology Reports, 2026)

Standardization of in vitro regeneration and genetic transformation protocol in Nerium oleander L. - Sandhya Prajapati; Renu Nimoriya; Rosani Kumari Shaw; Carol Janis Bilung; Anjum Bano; Dipak Kumar Mishra; Vineeta Tripathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Harnessing Potential of Phage Cocktail for Bacterial Reduction in Wastewater Treatment: A Pilot-Scale Demonstration of a Sustainable Approach - Smita Menon; Sandhya Shrivastava; Zarine Bhathena (Indian Journal of Microbiology, 2026)

Development of Panel of Three-Dimensional Biomarkers to Identify Gastric Carcinoma and Precancerous Lesions of the Stomach - An Analytical Cross-Sectional Study - Sandhya Karra; Ramanan Sinduja; Balakrishnan Gurushankari; T. P. Elamurugan; Thulasingam Mahalakshmy; Vikram Kate; Nivedita Nanda; Nachiappa Ganesh Rajesh; Murugesan Rajeswari; Ruben Raj; Gomathi Shankar (Indian Journal of Clinical Biochemistry, 2026)

Effects of plasma and magnetic field treatments on cereal crop physiology, productivity and gene expression. A review - Niharika Sharma; Sandhya Verma; K. N. Guruprasad (Acta Physiologiae Plantarum, 2026)

Plasma pTau181 is associated with subjective cognitive concerns but not objective cognitive decline or structural brain integrity measures in midlife - Ashleigh Barrett-Young; Erin E. Cawston; Brigid Ryan; Wickliffe C. Abraham; Antony Ambler; Tim Anderson; Kirsten Cheyne; Elizabeth Goodin; Sean Hogan; Renate M. Houts; David Ireland; Annchen R. Knodt; et al. (GeroScience, 2026)
Although plasma pTau181 has been shown to accurately discriminate patients with Alzheimer’s disease from healthy older adults, there are few studies of plasma biomarkers among middle-aged populations. Given the potential utility of plasma AD biomarkers such as pTau181 in screening for disease risk, examining pTau181 in a middle-aged cohort without AD is important for future implementation. The objectives of this study were to characterise plasma pTau181 in a middle-aged birth cohort aged 45 years and to investigate associations with early indicators of dementia risk. Participants were members of the Dunedin Multidisciplinary Health and Development Study, a longitudinal study of 1037 people born in New Zealand in 1972–1973. Plasma pTau181, self-reported cognitive concerns, MRI-based brain structure, and DunedinPACE (an epigenetic biomarker of biological ageing) were measured at age 45; cognition was measured in childhood and age 45. Plasma pTau181 concentrations at age 45 ( n = 854, 49% female) were associated with self-reported cognitive concerns (β = 0.09, p = .008); however, no significant associations were observed with objective cognitive decline, worse structural brain integrity, or biological ageing. Higher plasma pTau181 was associated with self-reported cognitive concerns at age 45, but not objective AD-related measures. The association of plasma pTau181 and self-reported cognitive concerns in this cohort suggests that AD pathology may begin to accumulate by age 45 and may be associated with subtle changes in cognition that are not at objectively measurable levels. Graphical Abstract

Traditional nets, modern pollution: Catching debris in Vembanad estuary India - Deepthi K.S.; Manju Lekshmi N.; Ranjeet K.; Sandhya K.M. (Regional Studies in Marine Science, 2026)

Artificial intelligence-based solar radiation forecasting for efficient use of renewable power plants - Vishal Sorathiya; Sanjeev Kumar Mandal; Sandhya Umrao; Keerti Rai; Pavan Chaudhary; Sumitra Padmanabhan (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Investigation of Atmospheric Boundary Layer Dynamics Over the Himalayan Foothill Region: Insights from Ground-Based LiDAR Observations and WRF Model - Shuchita Srivastava; Sandhya Singh; Som Sharma; Pooja Jindal; C. Aparna; Yogesh Kant; Debashis Mitra; Dharmendra Kumar Kamat; Aniket Patel; R. P. Singh; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Exploring the role of circRNA-miRNA-mRNA interactions in cervical cancer progression: insights into HPV status and potential therapeutic approaches - K. J. Sindhu; Venkatesan Nalini; Sundaram Sandhya; Devarajan Karunagaran (Journal of Applied Genetics, 2026)

Acute systemic DNA damage-related biomarker responses in adult orthodontic patients following radiographic investigations - Sandhya Murali; Nandhini Kannan; Vignesh Kailasam; Venkatachalam Perumal; Mohammed Mandodi (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Assessing Environmental Impacts Under Different Energy Mix Scenario for Non-Potable Water Reclamation in Domestic Wastewater Treatment Plant from a Megacity - Ardhy Yuliawan Norma Sakti; Sandhya Babel (Water Conservation Science and Engineering, 2026)

Unveiling the secret lives of endemic plants and understanding exclusive species of Gujarat, India through ecological niche modelling - Pankajkumar C. Prajapati; G. Sandhya Kiran; Agradeep Mohanta; Kavi K. Oza; Shrishti Rajput (Plant Ecology, 2026)

Comparison of Pediatric and Adult Glucagon-Like Peptide-1 Receptor Agonist Exposures Reported To United States Poison Centers, 2017–2024 - Anjali Senthilkumar; Hannah L. Hays; Sandhya Kistamgari; Natalie I. Rine; Allison L. Rhodes; Christopher E. Gaw; Gary A. Smith (Journal of Medical Toxicology, 2026)
Introduction As glucagon-like peptide-1 receptor agonist (GLP-1) use has increased among children, a better understanding of the related adverse effects in this population is needed. Methods National Poison Data System data from 2017 to 2024 were analyzed to compare characteristics and trends of exposures involving GLP-1s reported to United States (US) poison centers (PCs) among children 6–17 years old with those of adults. Results There were 13,924 single-substance GLP-1 exposures reported to US PCs from 2017 to 2024. The rate of exposures per one million US population increased by 1,830.8% from 0.97 in 2017 to 18.79 in 2024, including a 4,805.0% increase among children 6–17 years old from 0.04 in 2017 to 1.97 in 2024, with the majority of the increase occurring after 2021. Most exposures (91.7%) were associated with no or mild effects, while moderate effects were observed in 8.0% and major effects occurred in 42 exposures; there were two deaths. Children 6–17 years old were more likely (RR: 2.66, 95% CI: 1.73–4.11) to be admitted than adults, and children 12–17 years old were more likely (RR: 1.68, 95% CI: 1.08–2.63) to experience a more serious medical outcome than adults. Children 6–17 years old with at least one clinical effect experienced vomiting (88.2%) more commonly than adults (61.3%) (RR: 1.44, 95% CI: 1.34–1.55). Additionally, exposures among children 6–17 years old were more likely to be attributable to intentional misuse (RR: 8.12, 95% CI: 6.47–10.17) than among adults. Conclusions This study provides national-level, real-world findings that may help inform clinical practice.

In-silico studies on effective phytochemicals of Crocus sativus, Ocimum tenuiflorum and its modifications targeting NIPAH virus - Arsha S. Nair; D. K. S. Lekshmi; Bhavya Bhadran; K. S. Sandhya (In Silico Pharmacology, 2026)

Comparative evaluation of larval susceptibility of Culex quinquefasciatus and Culex gelidus to three formulations of Bacillus thuringiensis var. israelensis - Sandhya Ananth; S. Mahalakshmi; V. Pranav; Dharani Govindasamy; Ashwani Kumar (International Journal of Tropical Insect Science, 2026)

Leveraging a tailor-made approach to enhance the kinetics of a native ureolytic bacterium, Sporosarcina pasteurii PS3A, for effective bio-cementation - Syamili Sarma; Sandhya Sekhar; Anil Kumar Mishra (Bioresource Technology, 2026)

Waste to wealth: sustainable approach of alchemizing mushroom SMS into bioenergy - Garima Gupta; Sandhya Maurya; Durgesh Singh (Bioresource Technology, 2026)

Rice yields and climate change: impacts and adaptation in Southern India - Sandhya Neelima Atla; Anantha Rama Rao Chitiprolu; Nirmal Ravi Kumar Kotamraju; Srinivasa Rao Vatluri; Rama Devy Mulpuri (Theoretical and Applied Climatology, 2026)

Assessing water-use-efficient irrigation strategies for wheat (Triticum aestivum L.) in Uttarakhand by using the AquaCrop model - Sandhya Sharma; Kritika Kothari (Irrigation Science, 2026)

Genetic and genomic resources of Vigna species for their utility in advanced breeding - Kuldeep Kumar; Sudhir Kumar Jha; B. Manu; Adarsh Kumar; Vaibhav Kumar; Khela Ram Soren; Meenal Rathore; Sandhya Sharma; Kishor Gaikwad (Biologia Futura, 2026)

Fungal Foe Unveiled: AlphaFold-based 3D structure prediction of Rhizopus delemar 1,3-β-Glucan synthase and virtual screening for the identification of potential inhibitors - Sandhya Kushwaha; Deevena Kumari; Sonia Kumari; M. Elizabeth Sobhia (In Silico Pharmacology, 2026)

Land-use influence on soil microplastic pollution in Thailand: Implications for sustainable land management - Hewawasam Udumullage Erangi Imasha; Sandhya Babel (Environmental Monitoring and Assessment, 2026)

Homocysteine as a Dual Vasculo-Metabolic Risk Factor for Cognitive Impairment Specific to the Indian Context: A Systematic Review and Meta-Analysis - G. Sandhya; Mrinalini Rajashekhar; Thomas Gregor Issac (Indian Journal of Clinical Biochemistry, 2026)

Mitigation of chromium toxicity in Ocimum basilicum L. under the synergistic impact of biochar and Trichoderma yunnanense (NBRICRF_97) - Priya Dubey; Aditi Roy; Sandhya Mishra; Sampurna Nand; Mariya Naseem; Ruchi Chauhan; Alvina Farooqui; Anju Patel; Puja Khare; Pankaj Kumar Srivastava (Physiology and Molecular Biology of Plants, 2026)

Cultural, pathogenic and genetic variability of Rhizoctonia solani isolates incitant of rice sheath blight disease - Y. Sandhya; M. Reddi Kumar; P. Madhusudhan; P. Sudhakar; P. Lavanya Kumari (Vegetos, 2026)

Routing enabled optimization and deep recurrent VGG-16 model for plant disease detection in IoT - Kanagavalli Neelakandan; Sandhya Nadella; Balajee Maram; Madan Lal Saini (Computers and Electronics in Agriculture, 2026)

First report of the fiery box jellyfish Morbakka virulenta (Kishinouye, 1910) in Indian waters identified through integrative taxonomy - Ajay Kumar Jena; R. Amal; S.V. Sandhya; M. Aparna; Biraja Kumar Sahu (Regional Studies in Marine Science, 2026)

The role of phytochemicals from traditional and medicinal plants in the treatment and inhibition of colon cancer exploring different pathways - Hitarth Sah; Sandhya S (Next Research, 2026)

Unveiling the novel biodegradation mechanisms of acephate by Pandoraea pnomenusa: Catalytic pathway, functional enzyme, and environmental bioremediation - Ziqiu Lin; Mingqiu Liu; Shimei Pang; Wen-Juan Chen; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Bioresource Technology, 2026)

Atmospheric Microplastics Analysis: Discrepancies, Issues, and Way Forward - Yubraj Dahal; Sandhya Babel (Water, Air, & Soil Pollution, 2026)

Integrated Impacts of Microplastics Contaminated Compost on Soil–Plant Systems and Bioaccumulation in Lettuce, Tomato, and Radish - Hewawasam Udumullage Erangi Imasha; Sandhya Babel; Rujira Tisarum; Suriyan Cha-um (Water, Air, & Soil Pollution, 2026)

Genomic Characterization of F-box Genes in Pigeonpea (Cajanus cajan (L.) Millspaugh): Insights into Evolution, Synteny, and Spatio-Temporal Expression During Ovule/Seed Development - Kumari Arpita; Sandhya Sharma; Arvind Kumar Yadav; Machindra Nirgude; Mohammad Israil Ansari; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Hacking heterocysts: advances in the genetic regulation of heterocyst differentiation - Sandhya Deora; G. S. Deora; Subhasha Nigam; Harish (Archives of Microbiology, 2026)

Smart Hybrid Microneedle-Transferosome Platforms for Co-delivery of Peptide Biologics and Gene Modulators: Emerging Horizons in Targeted Transdermal Therapeutics - S. Sandhya; Prakash S. Goudanavar; Prasiddhi Naik (International Journal of Peptide Research and Therapeutics, 2025)

Efficient in vitro regeneration through leaf-derived callus in Origanum majorana (L.): a multipurpose medicinal plant - Dulam Sandhya; Phanikanth Jogam; Gulab Khan Rohela; Syam Prasad Sura; Rajender Vadluri; Mahipal S. Shekhawat; Sadanandam Abbagani (Vegetos, 2025)

Application of otolith morphology to unveil the stock structure of Hilsa shad (Tenualosa ilisha) in the Bhagirathi-Hooghly river system and the associated Northern Bay of Bengal - Sajina A.M.; Sangeetha M. Nair; Suresh V.V.R.; T. Maity; J. Mukherjee; S.K. Banik; Sandhya K.M.; R.K. Manna; R. Samanta (Regional Studies in Marine Science, 2025)

Bacillus subtilis as a powerful weapon in the removal of environmental pollutants - Mingqiu Liu; Wen-Juan Chen; Guiling Si; Chenxi Yan; Haoran Song; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

Comparative evaluation of pulsed electric field and assisted technology alkalization on the quality characteristics of cocoa powder - S Harish; K Sandhya; Vincent Hema; Ashish Rawson; Venkatachalapathy Natarajan (Innovative Food Science & Emerging Technologies, 2025)

Chroococcus minor cathode and polyphenolic mediated anode for enhancing bioenergy and bioremediation in a novel microbial desalination cell - Sandhya Prakash; Samsudeen Naina Mohamed; Kalaichelvi Ponnusamy (Environmental Pollution, 2025)

Effects of desiccation and liquid nitrogen exposure on seeds of dragon fruit (Hylocereus costaricensis) - Sandhya Gupta; Tushar Yadav; S.E. Topno (Cryobiology, 2025)

Neurons and neural networks to model proteins and protein networks - Sandhya Samarasinghe; Tran Nguyen Minh-Thai; Komal Sorthiya; Don Kulasiri (BioSystems, 2025)

Comparative metagenomic analysis of bacterial communities associated with two mealybug species, Phenacoccus saccharifolii and Dysmicoccus carens infesting sugarcane in Tamil Nadu, India - Sandhya Namadara; Ayyamuthu Rajarathinam Uma Pragadeesh; Sivakumar Uthandi; Anandham Rangasamy; Kannan Malaichamy; Manivannan Venkatesan; Manikanda Boopathi Narayanan; Senthilkumar Murugaiyan (World Journal of Microbiology and Biotechnology, 2025)

Assessment of genetic diversity and population structure analysis in Himalayan garlic genotypes from Sikkim using SSR markers - Lomash Sharma; Rajesh Kumar; Kime Tare; Sandhya Lamichaney (Molecular Biology Reports, 2025)

Enhanced Delivery of Methotrexate for Scalp Psoriasis Treatment via Nanosuspension Hair Dye: A Box-Behnken Optimization Approach - Poojitha P.N.; Akhil Perumalla; Sandhya Rachamalla; shirisha Mandli; Shilpa Ajje; Sindura Talari; Shaik Afroz Kottapalli; Nagashubha B; M. Kiran Sai (Journal of Pharmaceutical Innovation, 2025)

Effect of explant sources, sonication combined with vacuum infiltration, and biochar on improving Agrobacterium-mediated transformation efficiency in Eucalyptus camaldulensis - M. C. Sandhya; Sreeja Sahadevan; Krishnaraj Shamili; Manoj Kumar Rajendran; Harshita Singh; Aiyar Balasubramanian; Muthukrishnan Arun; Sivakumar Veerasamy; Mathish Nambiar-Veetil (Plant Biotechnology Reports, 2025)

Delving into the BURP Super family: A Comprehensive QTL-Assisted Study on RD22 genes and its Role in Salinity Stress Tolerance in Chickpea - Sandhya Tripathi; Chellapilla Bharadwaj; Maloti Hembram; Neeraj Kumar; Aravind K. Konda; B. Mondal; N. C. Gupta; G. P. Dixit; K. R. Soren (Biochemical Genetics, 2025)

Tree‐Ring Inferred Seven Century Long Snowfall Record From the Cold‐Arid Western Himalaya, India - Krishna G. Misra; Vikram Singh; Ram R. Yadav; Sandhya Misra (International Journal of Climatology, 2025)
In the present study, Himalayan cedar samples from eight climate‐stressed sites were collected and used to examine the snowfall variability over the Lahaul‐Spiti region. The tree‐growth and climate relationship was explored using response function analysis, which revealed a positive tree‐growth relationship with precipitation and a negative relationship with temperature. The response function analysis also suggested that cool and moist climatic conditions favour tree growth, while warm and dry conditions reduce tree radial growth over the Lahaul‐Spiti region. Taking this relationship as a guide, we further tested the relationship of tree‐ring chronologies with observational Snow Water Equivalent (SWE) data. An observed statistically significant positive correlation encouraged us to develop the linear regression model for reconstruction. The linear regression models were used to develop a new November to April SWE record for the cold‐arid Lahaul‐Spiti region, Himachal Pradesh. The SWE reconstruction extends back to AD 1290 and revealed low SWE values in the year 1626 (223.6 mm), 1970 (254.4 mm), 1329 (270.1 mm), 1705 (271.9 mm), 2008 (278.5 mm), and high SWE values in the year 1306 (791.7 mm), 1348 (771.0 mm), 1412 (769.7 mm), 1569 (769.1 mm) and 1661 (765.9 mm). The reconstructed SWE is consistent with available precipitation, drought, and river flow records developed from different regions of the western Himalaya, underpinning its importance in understanding the regional hydro‐climatic variability. The cross‐field correlation analysis of the present SWE record with gridded precipitation, PDSI, and MADA also revealed a significant correlation for the westerly dominated Himalayan regions. The positive spatial correlation of SWE with snow cover area of the Northern Hemisphere further endorses the strength of our reconstruction. We also noted strong linkages of SWE with the El‐Niño Southern Oscillation in the present study, while the dominance of the Indo‐Pacific climate system is observed in the spectral analysis. Therefore, we believe that our attempt to develop a seven‐century‐long SWE record from a data‐scarce Himalayan region will strengthen our understanding of the hydrological variations in the long‐term perspective.

Caenorhabditis elegans: Origins and use as a modern model organism - Kavita Babu; Sandhya P Koushika (Journal of Biosciences, 2025)

Biodegradation of the widely used amide herbicides: Microbial resources, catabolic pathways and molecular mechanisms - Guiling Si; Quanhong Zhang; Mingqiu Liu; Wen-Juan Chen; Yuting Tong; Parul Chaudhary; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

Tailoring chickpea protein functionality for food applications through supercritical CO2 processing - Gomathy Sandhya Subramanian; Daryl Lee; Su Hui Lim; Sergey Gorelik; Celyne Halim; Ashley Lim; Shi Jie Ang; Dylan Hao Wen Swee; Uma Jingxin Tay; Sreenivasa Reddy Puniredd; Khin Yin Win; Yoganathan Kanagasundaram; et al. (Food Research International, 2025)

Biparental plastid inheritance and its implications in plastid genome engineering - Sandhya Yadav; Dipanshu Ghosh; Twinkle; Vivek Dogra (Plant Cell Reports, 2025)

Anti-leishmanial activity of synthesized and characterized semisynthetic derivatives of betulin - Aanchal Loshali; Vidhu Aeri; Sandhya Bawa (Phytochemistry Letters, 2025)

Semi-synthetic ecdysteroids as promising new antichagasic agents - Márton B. Háznagy; Máté Vágvölgyi; Sandhya R. Krishnan; Kaushavi Cholke; Jürg Gertsch; Attila Hunyadi (Phytochemistry Letters, 2025)

Coumarin polypharmacology and elucidation of an underlying molecular mechanism of action - Sandhya Krishnan; Felix Huwyler; Lukasz Kurach; Krystyna Skalicka-Wozniak; Jürg Gertsch (Phytochemistry Letters, 2025)

Grafting nanostructures of metal oxides onto activated carbon fiber felt for enhanced removal of divalent ions in capacitive deionization - Thong Nguyen Tan; Sandhya Babel (Journal of Environmental Chemical Engineering, 2025)

Development of Or-gene-based co-dominant markers and their utilization in marker-assisted breeding for ß-carotene biofortification in different maturity groups of cauliflower - Shrawan Singh; Vinay Verma; Bhagchand Shivran; Rahul Kumar Meena; Anamika Chandel; Sandhya Saroha; Navinder Saini (Theoretical and Applied Genetics, 2025)

Cryopreservation research for long term conservation of Artocarpus lacucha Buch. -Ham. genetic resources - Rinky Resma Panda; Ramesh Chandra; Sandhya Gupta (Genetic Resources and Crop Evolution, 2025)

Soil bacterial diversity and its functions shift under varying chromium concentration in tannery waste dumpsite - Sandhya Mishra; Priyamvada Mishra; Priya Dubey; Mariya Naseem; Anju Patel; Meher H. Asif; Pankaj Kumar Srivastava (Environmental Sustainability, 2025)

Localization of mitochondria along axons and at synapses in C. elegans touch receptor neurons is necessary for touch habituation - Sneha Hegde; Nayantara Varma; Parul Sood; Sandhya P Koushika (Journal of Biosciences, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Revealing drought tolerance mechanisms in Pongamia pinnata through integrated physiological, biochemical, and transcriptomic profiling - K. Rajarajan; Sandhya Sharma; Harsha Srivastava; Kumari Arpita; A.K. Handa; A. Arunachalam; S.K. Dhyani (Plant Gene, 2025)

Assessing ecological sustainability of the Narmada River using the macrophyte river index - Sandhya Saini; Tarun Kumar Thakur; Saebugari Balaswamy; Amit Kumar; Ramesh Raj Pant; Rupesh Kumar; Mohammad Rafe Hatshan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Amino acid metabolism in cervical cancer: Mechanisms and implications in therapy - Roopak Murali; Sivapriya Singaraj; Isha Govindh; Pooja Singh; Sandhya Sundaram; Satish Srinivas; Gopal Gopisetty; Harish C. Chandramoorthy; Rajesh Kumar Gandhirajan (Next Research, 2025)

Simulation study of effect of absorber layer thickness and ambient temperature on photovoltaic performance of CZTSe solar cells - Vikas Kumar Rajput; Rashmi; Sandhya Mann; A.S. Mathur; B.P. Singh (Next Research, 2025)

Two Evolutionary Diverged Liverworts that Shared the Same Habitats Developed a Few Distinct Seasonal Adaptive Strategies: Insights from a Transcriptomic Approach - Suvajit Basu; Sandhya Yadav; Vishal Kumar Jha; Subhankar Biswas; Akanksha Srivastava; Kritika Tripathi; Raju Mondal; Neha Chaurasia; Sushil Kumar Singh; Yogesh Mishra (Plant Molecular Biology Reporter, 2025)

Molecular insights into two wild edible mushrooms from Jammu and Kashmir, India - Ayushi Mahajan; Sandhya Rajput; Komal Verma; Yash Pal Sharma (Indian Phytopathology, 2025)

Genomics data reveals DNA polymorphism associated with seed number per pod (SNPP) in pigeonpea, Cajanus cajan (L.) Millsp. - Akash Paul; Kuldeep Kumar; Machindra Nirgude; Antara Das; Sandhya Sharma; Kishor Gaikwad (The Nucleus, 2025)

Seaweed as a sink for microplastic contamination: Uptake, identifications and food safety implications - Ravi Harini; K. Sandhya; C.K. Sunil; Venkatachalapathy Natarajan (Environmental Research, 2025)

Optimizing dilute sulfuric acid thermohydrolysis of dried food waste using the desirability function to produce a fermentation-friendly hydrolysate for biohydrogen production - Julkipli Julkipli; Sandhya Babel (Biomass and Bioenergy, 2025)

Unveiling the Spatio-Temporal Dynamics of Son Beel: A Freshwater Wetland from Indian East Sub-Himalaya - Ganithi Sandhya; Subrata Nandy; Hitendra Padalia; Anisha Dey; Arun Jyoti Nath; Koushik Majumdar; Ashesh Kumar Das (Journal of the Indian Society of Remote Sensing, 2025)

Impact of home gardens promoted among urban residents in Dhaka, Bangladesh - Pepijn Schreinemachers; Sandhya S. Kumar; Nasir Md. Uddin (Food Security, 2025)
Promoting gardening among urban residents holds the potential to improve urban diets in low- and middle-income countries, but there is a lack of evidence of impact. This study tests the hypothesis that training urban residents in gardening increases their intake of fruit and vegetables. It uses panel data for 254 control and 425 treatment households from four city corporations in the Dhaka metropolitan area of Bangladesh. Urban residents, 85% of whom were women, were interviewed before the start of an urban gardening program and one year after training and inputs were provided to the treatment group. The study estimated the average treatment effects using a difference-in-difference estimator. Of the 38 outcomes tested, 20 are significant (p < 0.05) with 19 indicating a beneficial effect and one indicating an adverse effect. Among the beneficial effects, there is an increase in the diversity of fruits and vegetables produced (+ 5 species, p < 0.01), the frequency of harvesting (+ 0.64 times/week; p < 0.01), and increased sharing of produce with neighbors (+ 8%, p < 0.01). Regarding food and nutrition, there is an increase in women’s dietary diversity score (+ 0.37 on a 0–10 scale; p < 0.01), women’s minimum dietary diversity (+ 4%; p < 0.01), and in the number of portions of cooked vegetables eaten (+ 0.96 portions/day; p < 0.01). The gardening intervention also contributes to a range of perceived social, personal, and psychological benefits. The adverse effect is an increase in ultra-processed food consumption (+ 19%, p = 0.04). Nevertheless, the results confirm that urban gardening interventions can improve the quality of urban diets alongside other benefits.

Macrophages co-loaded with drug-associated and superparamagnetic nanoparticles for triggered drug release by alternating magnetic fields - Omkar Desai; Sandhya Kumar; Mario Köster; Sami Ullah; Sushobhan Sarker; Valentin Hagemann; Mosaieb Habib; Nicole Klaassen; Silke Notter; Claus Feldmann; Nina Ehlert; Hansjörg Hauser; et al. (Drug Delivery and Translational Research, 2025)
Two features of macrophages make them attractive for targeted transport of drugs: they efficiently take up a broad spectrum of nanoparticles (NPs) and, by sensing cytokine gradients, they are attracted to the sites of infection and inflammation. To expand the potential of macrophages as drug carriers, we investigated whether macrophages could be simultaneously coloaded with different types of nanoparticles, thus equipping individual cells with different functionalities. We used superparamagnetic iron oxide NPs (SPIONs), which produce apoptosis-inducing hyperthermia when exposed to an alternating magnetic field (AMF), and co-loaded them on macrophages together with drug-containing NPs (inorganic–organic nanoparticles (IOH-NPs) or mesoporous silica NPs (MSNs)). We show that individual macrophages can take up both SPIONs and drug-loaded NPs efficiently, thereby generating drug-loaded cells susceptible to AMF-induced cell death. Macrophages co-loaded with SPIONs and drug-containing IOH-NPs spontaneously released the drugs at similar rates irrespective of the application of an AMF. Notably, while the spontaneous drug release from macrophages co-loaded with SPIONs and drug-associated MSNs was low, AMF exposure accelerated the drug release. Thus, AMF exposure of SPION/drug-MSN coloaded macrophages provides a simple strategy for trigger-controlled drug release since it does not require any chemical modification of NPs or drugs. Thus, we assume that the coloading of different types of NPs will expand the potential of macrophages for drug delivery. Graphical Abstract

Description of Stieleria mannarensis sp. nov., isolated from a marine sponge, and proposal to include members of the genus Roseiconus in the genus Stieleria - Nicolai Kallscheuer; Gaurav Kumar; Shabbir Ahamad; Sandhya Duddeda; Chintalapati Sasikala; Christian Jogler; Chintalapati Venkata Ramana (Antonie van Leeuwenhoek, 2025)
A pink-coloured, salt- and alkali-tolerant strain, JC639 T , was isolated from a specimen of the marine sponge Spheciospongia sp. The novel isolate is motile, aerobic and forms oval to pear-shaped cells. It shares the highest 16S rRNA gene sequence identity with Stieleria neptunia Enr13 T and Stieleria maiorica Mal15 T in the family Pirellulaceae (phylum Planctomycetota ). Optimum pH and temperature for growth are 8.0 (range 7.0–10.0) and 25 °C (range 10–30 °C), respectively. Major fatty acids are C 15:1 ω8c, C 16:0, C 18:1 ω9c, C 18:0 , and C 16:1 ω7c/C 16:1 ω6c. Major polar lipids are phosphatidylcholine and phosphatidylethanolamine. The genome of strain JC639 T has a size of 9.56 Mb and a DNA G + C content of 59.5%. The polyphasic analysis of the isolate supports its delineation from the known species in the genus Stieleria . We therefore introduce Stieleria mannarensis sp. nov., represented by JC639 T (= KCTC 72168 T = NBRC 113878 T ) as the type strain. Based on an analysis of established phylogenomic markers performed with all current members of the overlapping genera Stieleria and Roseiconus , we further propose to include the two so far characterized Roseiconus species in the genus Stieleria .

Healing power of Neltuma juliflora (Sw.) Raf.: a comprehensive review of its phytochemicals, pharmacology aspects, and potential health benefits - S. Deepthi; K. Narsimha; K. Ashwini; M. Sandhya Rani; K. Suresh Babu (Natural Product Research, 2025)

Advancements in maize leaf disease detection, segmentation and classification: A review - Suresh Timilsina; Sandhya Sharma; Satoshi Kondo (Biosystems Engineering, 2025)

CRISPR/Cas9: efficient and emerging scope for Brassica crop improvement - Shiv Shankar Sharma; Ashwani Pandey; Anamika Kashyap; Lakshay Goyal; Pooja Garg; Ranjeet Kushwaha; Jyoti Sharma; Shikha Tripathi; Sujata Kumari; George Thomas; Malkhey Verma; Navin C. Gupta; et al. (Planta, 2025)

Cultivation of Scenedesmus obliquus NCIM 5526 in a sol–gel transition medium for lipid production - V Varshini; R V Anusha Gowri; S Sandhya; L A Nirmal; S Jacob (International Journal of Environmental Science and Technology, 2025)

Microbial Diversity and Organoleptic Properties in Traditionally Fermented Pineapple Beverage Ameliorated with Blueberry or Pomegranate - Prattipati Geya Sai Manjusha; Annamaneni Sandhya; Bee Hameeda (Current Microbiology, 2025)

Processing and utilization of sweet lime pomace in low glycemic wheat flour formulation - Darshan S. Munot; Sandhya R. Shewale; Debashis Kundu (Next Research, 2025)

Unlocking the potential of parboiled rice mill effluent: From microalgae cultivation to bioelectricity production for sustainable development - K. Sandhya; C.K. Sunil; J.A. Moses; Mahendran Radhakrishnan; Venkatachalapathy Natarajan (Journal of Environmental Management, 2025)

Electrochemical sensors for monitoring water quality: Recent advances in graphene quantum dot-based materials for the detection of toxic heavy metal ions Cd(II), Pb(II) and Hg(II) with their mechanistic aspects - Saisree S.; Arya S. Nair; Elsa Dais; Sandhya K.Y. (Journal of Environmental Chemical Engineering, 2025)

SK609, a novel dopamine D3 receptor agonist and norepinephrine transporter blocker with putative pro-cognitive actions, does not induce psychostimulant-like increases in risky choice during probabilistic discounting - Christopher P. Knapp; Brooke Fallon; Sandhya Kortagere; Barry D. Waterhouse; Stan B. Floresco; Rachel L. Navarra (Psychopharmacology, 2025)
Rationale Psychostimulants, such as amphetamine (AMPH) and methylphenidate (MPH), non-selectively elevate extracellular concentrations of the catecholamine neurotransmitters, dopamine (DA) and norepinephrine (NE), and are common pharmacological strategies used to improve prefrontal cortex (PFC)-dependent cognitive dysfunction. However, this approach can be problematic given AMPH has been shown to increase preference for risky choices in a rodent assay of risk/reward decision making. SK609 is a novel NE reuptake blocker that selectively activates DA D3 receptors without affinity for the DA transporter. SK609 has been shown to improve cognitive performance without increasing psychostimulant-like spontaneous locomotor activity, suggesting SK609 may benefit neurocognitive function without psychostimulant-like side effect liability. Objectives We compared AMPH, MPH, and SK609 within dose ranges that display their cognitive enhancing properties in a probabilistic discounting task (PDT) of risk/reward decision making behavior to assess their potential to increase risky choice preference. Methods Rats chose between small/certain rewards delivered with 100% certainty and large/risky rewards delivered with descending probabilities across a session (100 − 6.25%) following administration of AMPH (0.25-1 mg/kg), MPH (2–8 mg/kg), and SK609 (4 mg/kg). Results AMPH and MPH increased risky choice behavior at doses previously reported to enhance cognition, whereas SK609 did not. AMPH and MPH also reduced sensitivity to non-rewarded risky choices. Conclusions These data highlight the combination of NE transporter blockade and selective D3 activation in pro-cognitive action without psychostimulant-like side effect liability. The absence of DA transporter blockade and non-selective dopaminergic activation are beneficial properties of SK609 that differentiates it from the traditional pro-cognitive psychostimulants.

Marine Life Ecosystem Analysis Based on Climate Change Detection Using Deep Learning Algorithms - B. Rebecca; A. Sandhya; Kiran Sree Pokkuluri; Gunipati Kanishka; Khasimbee Shaik; B. Murali Krishna (Remote Sensing in Earth Systems Sciences, 2025)

Potential regulation of cleistogamy in pigeonpea through jasmonic acid and bHLH transcription factor interactions - Palak Gupta; Harsha Srivastava; Kuldeep Kumar; Machindra Nirgude; Kumari Arpita; Jyothilakshmi Vadassery; Sandhya Sharma; Malik Zainul Abdin; Kishor Gaikwad (Plant Reproduction, 2025)

A new species of eight‐gilled hagfish ( M yxinidae: Eptatretus ) from the deep waters of the L akshadweep S ea, I ndia - Treasa Augustina Areeprambil Xavier; Miriam Paul Sreeram; Sandhya Sukumaran; Akhilesh Kalli Valappil; Sreekumar Kaippaparambil Manikandan; Grinson George (Journal of Fish Biology, 2025)
A new species of eight‐gilled hagfish genus Eptatretus (Myxinidae) is described based on five specimens trawled on the upper continental slope off Kollam, Kerala, India, northern Indian Ocean. Eptatretus gopali sp. nov. can be diagnosed by the presence of eight‐gill pouches and gill apertures, 10–11 pre‐brachial, 7 branchial, 50–55 trunk, 9–10 tail slime pores, 77–82 total pores, 3/2 multicusp teeth pattern, 40–44 total cusps, absence of nasal‐sinus papillae, and a light brown body color. Detailed morphological comparisons with all known eight‐gilled species of Eptatretus showed that the new species was distinct from all others by having 40–44 total cusps, characteristic body proportions, and the shortest tail length. E. gopali formed a district clade in the phylogenetic tree and exhibited a genetic distance of 3.6%–11.6% in Cytochrome C oxidase I (COI) sequences and 2.0%–4.9% in 16S rRNA sequences between the congeners. An identification key is also provided for the species of Eptatretus from the Indian Ocean.

Early Detection of Plant Diseases and their Management Using Quantum Dots: Status and Strategies - Maddi Sandhya; Govindasamy Senthilraja; Eswaran Priyadharshini; Lingareddy Usha Rani; Rathinakumar Harideekshayini; Moorthy Nishanthi; Theerthagiri Anand; Kizhaeral Sevathapandian Subramanian (Journal of Fluorescence, 2025)

On the role of Sri Lankan land mass in safeguarding the southeastern coast of India from Southern Ocean swell attacks - K G Sandhya; R Harikumar; P A Francis; Balaji Baduru; T M Balakrishnan Nair (Journal of Earth System Science, 2025)

Microplastics in agricultural soils following sewage sludge applications: Evidence from a 25-year study - Stuart J.F.F. Ramage; Malcolm Coull; Patricia Cooper; Colin D. Campbell; Radhakrishna Prabhu; Kyari Yates; Lorna A. Dawson; Sandhya Devalla; Eulyn Pagaling (Chemosphere, 2025)

Integrating MnO2 nanostructures into activated carbon fiber felt for enhanced chromium ions removal in capacitive deionization - Thong Nguyen Tan; Sandhya Babel (Process Safety and Environmental Protection, 2025)

Exploring the floral diversity in honey from various regions of Bangladesh using Melissopalynology - Pratik Raj Karki; Md. Mamunur Rahman; Sandhya Subedi; Aroni Preya Biswas; Disha Mallick; Md. Nahidul Islam (Food and Humanity, 2025)

EAAT2 Activation Regulates Glutamate Excitotoxicity and Reduces Impulsivity in a Rodent Model of Parkinson’s Disease - Sanjay Das; Kyle Mccloskey; Binod Nepal; Sandhya Kortagere (Molecular Neurobiology, 2025)
Parkinson’s disease (PD) is a systemic disease characterized by motor and nonmotor impairments. Loss of dopaminergic neurons in the substantia nigra pars compacta region in PD disrupts dopamine-glutamate homeostasis in the corticostriatal circuit, contributing to cognitive impairment. In addition, excitatory amino acid transporter-2 (EAAT2), localized predominantly to astrocytes and responsible for > 80% of synaptic glutamate clearance, is downregulated in PD, causing glutamate spillover and excitotoxicity. This altered dopamine-glutamate homeostasis and excitotoxicity may affect reward-mediated decision-making behaviors and promote impulsive behaviors in PD. In this study, we hypothesized that GTS467, a small-molecule activator of EAAT2, could effectively reduce excitotoxicity and treat cognitive impairment without promoting impulsive behavior in PD. Rats that were unilaterally lesioned with the 6-OHDA toxin to produce Parkinsonian symptoms were referred to as lesioned rats. Lesioned rats were trained to meet baseline criteria in a 5-choice serial reaction time task, and the chronic effects of GTS467 were assessed after 3 weeks of treatment. The results showed that chronic treatment with GTS467 significantly improved correct responses and reduced premature impulsive responses and omissions compared with saline treatment. This improvement in performance correlated with a reduction in glutamate levels, an increase in EAAT2 expression, and normalization of NMDA receptor subunit expression and signaling. Furthermore, transcriptomic studies on the prefrontal cortex tissue have shown the differential expression of genes involved in neuroprotection, neuroinflammation, learning, and memory. These results validate the role of glutamate excitotoxicity in promoting impulsive behaviors and suggest that GTS467 can be developed as a therapeutic agent to reduce cognitive impairment and impulsive behaviors in PD.

Evaluating terminal heat stress tolerance and genetic variation in emmer wheat (Triticum dicoccum L.) germplasm using morphological and molecular approaches - Meda Alekya; Jyoti Kumari; Jatin Tanwar; Preeti Jakhar; Abhijeet Mudhale; Sandhya Tyagi; Shivani Sharma; Neelu Jain; Jai Prakash Jaiswal; K. J. Yashavantha Kumar; Shailendra K. Jha (Euphytica, 2025)

Dual Metal Ion Sensing by an Azo Compound Derived from Thiazolo[3,2-a] Indole: A Selective and Sensitive Approach - Haitham K.R. Al-Sharifi; C. B. Meenakshy; K. S. Sandhya; Ani Deepthi (Journal of Fluorescence, 2025)

A geospatial analysis of coal mine overburden reclamation: Land use, carbon stock, biomass, and soil genesis in chronosequence plantations - Tarun Kumar Thakur; Digvesh Kumar Patel; Sandhya Saini; Anita Thakur; Singam Laxmana Swamy; Sanjeev Bakshi; Amit Kumar; Fohad Mabood Husain; Rupesh Kumar (Journal of Geochemical Exploration, 2025)

Soy lecithin strengthens amaranth protein-based omelettes through protein complexation which alters protein interactions - Uma Jingxin Tay; Joanne Yi Hui Toy; Chengxin He; Marco Vignuzzi; Xin Yang; Gomathy Sandhya Subramanian; Maria Antipina; Paolo Alberto Lorenzini; Weibiao Zhou; Dejian Huang (Food Structure, 2025)

Pediatric Exposures Associated with Caffeine Energy Products Reported to United States Poison Centers, 2011–2023 - Timothy R. Thompson; Hannah L. Hays; Sandhya Kistamgari; Natalie I. Rine; Motao Zhu; Henry Xiang; Gary A. Smith (Journal of Medical Toxicology, 2025)
Introduction This study investigated the characteristics and trends of pediatric exposures to caffeine energy products reported to US poison centers Methods National Poison Data System data for caffeine energy product single-substance exposures during 2011–2023 among individuals < 20 years old were analyzed. Results There were 32,482 caffeine energy product exposures reported to US poison centers with a 17.3% exposure rate increase during 2011–2023. Most exposures were among < 6-year-olds (69.6%), males (56.7%), or involved liquid formulations (57.5%). Most (80.7%) were not treated in a healthcare facility; however, 1.6% were medically admitted. Teenagers 13–19 years old were more likely to be medically admitted (OR = 12.74, 95% CI: 10.40–15.60) or have a serious medical outcome (OR = 18.83, 95% CI: 16.88–21.01) than children < 13 years old. Solid energy product formulations were more likely to be associated with a serious medical outcome (OR = 1.98, 95% CI: 1.81–2.17) or medical admission (OR = 5.23, 95% CI: 4.31–6.36) than other types of formulations. During the study period, exposure rates increased for liquid (34.5%) and powder/granules (632.9%) product formulations but decreased for solids (-51.5%). Among liquid formulation subcategories, the exposure rate for beverages increased (46.5%) and that for shots decreased (-86.1%). Conclusions Although most pediatric exposures to caffeine energy products reported to US poison centers were associated with no or minimal clinical effects, serious medical outcomes and medical admissions occurred. The product formulations that drove the 17% increase in the exposure rate changed during the study period. Opportunities exist to reduce the adverse effects of caffeine energy products among the pediatric population.

Further enrichment of targeted indole alkaloids through root-derived culture systems from Alstonia scholaris (L.) R.Br. - Carol Janis Bilung; Priyanka Rawat; Ankit Saxena; Rosani Kumari Shaw; Sandhya Prajapati; Sanjeev K. Shukla; Sanjeev Kanojiya; Dipak Kumar Mishra (In Vitro Cellular & Developmental Biology - Plant, 2025)

Retrieval of abandoned, lost, or otherwise discarded fishing gear through different retrieval modes and analysis of biota on the retrieved gear - Harsha Krishnankutty; Sandhya Kavitha Mandhir; Aishwarya Korassery Ajaya Ghosh; Mary Baby Kariyilaparambu Antony; Saly Narimattom Thomas (Environmental Science and Pollution Research, 2025)

Evaluating the effects of zinc oxide nanoparticles on a sentinel aquatic invertebrate species: Transcriptomic analysis and potential implications for ecosystem health - V.G. Vysakh; Sandhya Sukumaran; A. Gopalakrishnan (Marine Pollution Bulletin, 2025)

Hydrochemical Evaluation of Groundwater Quality and Human Health Risk Assessment of Fluoride and Nitrate: A Case Study of Pratapgarh District UP, India - Sandhya Maurya; Ashok B. More; Garima Gupta; Abhishek Saxena; Anjali Singh (Water, Air, & Soil Pollution, 2025)

Preliminary Estimates on Length-Weight Relationships and Condition Factor of Commercially Important Fishes from a Tropical Reservoir, Kerala, South India - Kavitha Mandhir Sandhya; Raju Saranya (Thalassas: An International Journal of Marine Sciences, 2025)

Nanotechnology-Based Modern Biosensors for the Detection of SARS-CoV-2 Virus - Sandhya Devi; Neha Yadav; Rakesh Yadav (Indian Journal of Microbiology, 2025)

First report of Curvularia lunata as causal agent of Curvularia blight in potato and tomato crops in Mauritius - Nooreen Mamode Ally; Sandhya D. Takooree; Vijayanti M. Ranghoo-Sanmukhiya; Hudaa Neetoo (Indian Phytopathology, 2025)

Comprehensive review of the microbial approach to Mealybug management - Sandhya Namadara; Sivakumar Uthandi; Anandham Rangasamy; Kannan Malaichamy; Manivannan Venkatesan; Manikanda Boopathi Narayanan; Senthilkumar Murugaiyan (International Journal of Tropical Insect Science, 2025)

Biochar for mitigating pharmaceutical pollution in wastewater: A sustainable solution - Sampurna Nand; Prem Prakash Singh; Swati Verma; Sandhya Mishra; Anju Patel; Siddharth Shukla; Pankaj Kumar Srivastava (Science of The Total Environment, 2025)

Bridging the gap: Seven new distributional records from the west coast of India with phylogenetic reconstruction of the Indian deep-sea Ophidiiformes - Treasa Augustina A.X.; Miriam Paul Sreeram; Sandhya Sukumaran; Anjaly Jose; Sreekumar K.M.; Bibin Xavier; Grinson George (Regional Studies in Marine Science, 2025)

Unveiling the hydrolase Oph2876 mediated chlorpyrifos degradation mechanism in Pseudomonas nitroreducens and its potential for environmental bioremediation - Haoran Song; Wen-Juan Chen; Shao-Fang Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Hazardous Materials, 2025)

Micro-Phyto-assisted reduction of Hexachlorocyclohexane (HCH) contamination in soil: A sustainable solution to mitigate HCH pollution - Aditi Roy; Priya Dubey; Sandhya Mishra; Poornima Vajpayee; Suchi Srivastava; Pankaj Kumar Srivastava (International Biodeterioration & Biodegradation, 2025)

Production of non-embryogenic synthetic seeds for short-term cold storage and ISSR marker-assisted genetic fidelity analysis of Coleus forskohlii (Willd) Briq. plants - Mahesh Kumar Badhepuri; Mahender Aileni; Prabhakar Rao Beeravelli; Sathish Kumar Durgam; Dulam Sandhya; Mahipal S. Shekhawat; Nageswara Rao Singisala (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Identifying the pollution sources of River Yamuna through field observations and participatory approach - Sayantan Samui; Arkadip Mallik; Dinesh Kumar; Sandhya Rao; C T Dhanya; Ashvani Kumar Gosain (Journal of Earth System Science, 2025)

Abundance and characteristics of atmospheric microplastics deposition in indoor and outdoor environments in Bangkok, Thailand - Yubraj Dahal; Sandhya Babel (Air Quality, Atmosphere & Health, 2025)

Efficient knockout of TOM1 gene using CRISPR/Cas9 in Indian tomato cultivar ‘Arka Vikas’ - Dulam Sandhya; Phanikanth Jogam; Vijay Sheri; Venkataiah Peddaboina; Venkateswar Rao Allini; Sadanandam Abbagani (Vegetos, 2025)

Prevalence and characteristics of microplastic contamination in soft drinks and potential consumer exposure - Anh Tuan Ta; Sandhya Babel; Li Pang Wang (Journal of Environmental Management, 2025)

Mechanistic insights into D-cyphenothrin biodegradation by Rhodococcus ruber Y14 and its potential for bioremediation of pyrethroid-polluted environment - Yaohua Huang; Shunkang Zhou; Wen-Juan Chen; Xiaofan Zhou; Shao-Fang Chen; Haoran Song; Zhenchen Yan; Sandhya Mishra; Mohamed A. Ghorab; Pankaj Bhatt; Shaohua Chen (Chemical Engineering Journal, 2025)

Addressing the Microplastic Pollution: A Societal Challenge - Minisha Udhayakumar; Shanmugapriya Udhayakumar; Subha Bharathi Pitchaimuthu; Sandhya Alagarsamy; Kayalvizhi Thirumalaisamy; Muhammad Azeem; Ramkumar Govindarajan; Karthiyaini Damodharan; Ayyappa Das Madhubala Parameswaran; Parimala Gnana Soundari Arockiam Jeyasundar (Water, Air, & Soil Pollution, 2025)

Pharmaceutical aspects of JAK inhibitors: a comparative review - Sandhya Jinesh; Rajan Radhakrishnan (Inflammopharmacology, 2025)

A hybrid approach: remote sensing, analytic hierarchy process and geographic information system for groundwater potential mapping in Dediapada, India - Garge Sandhya Kiran; Ramandeep Kaur M. Malhi; Agradeep Mohanta (Environmental Science and Pollution Research, 2024)

Targeted editing of susceptibility genes for plant disease resistance: Current state and future hopes - Lingareddy Usha Rani; Manisha Shelke; Maddi Sandhya; Govindasamy Senthilraja (Plant Gene, 2024)

Morphometric indices assessment: Implications for active tectonics in the upper Narmada Basin, central India - Digvesh Kumar Patel; Tarun Kumar Thakur; Sandhya Saini; Adesh Patel; S.C. Bhatt; Amit Kumar; Rupesh Kumar; Fohad Mabood Husain (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A paradigm assessment of low-cost ceramic membranes: Raw materials, fabrication techniques, cost analysis, environment impact, wastewater treatment, fouling, and future prospects - K.V.V. Satyannarayana; Randeep Singh; S. Lakshmi Sandhya Rani; M. Sreekanth; Vinoth Kumar Raja; Young-Ho Ahn (Journal of Water Process Engineering, 2024)

Removal of alachlor from the water/soil environments: The significance of microbial remediation and its biochemical mechanisms - Zeren Li; Mengyi Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Water Process Engineering, 2024)

Complete biodegradation of glyphosate with microbial consortium YS622: Structural analysis, biochemical pathways, and environmental bioremediation - Wenping Zhang; Wen-Juan Chen; Shao-Fang Chen; Mingqiu Liu; Mohamed A. Ghorab; Sandhya Mishra; Pankaj Bhatt; Shaohua Chen (Journal of Environmental Chemical Engineering, 2024)

Cryo-conservation of temperate berry crops at ICAR-NBPGR - Sandhya Gupta; Narender Negi; Sheikh M. Sultan (Cryobiology, 2024)

Impact of plant-derived electron shuttles on the exoelectrogens for enhanced novel microbial desalination cell performance - Sandhya Prakash; Samsudeen Naina Mohamed; Kalaichelvi Ponnusamy (Chemical Engineering Journal, 2024)

Yield loss and growth-defense trade-offs: impact of engineering amino acid transporters - Pinky Dhatterwal; Manoj Prasad; Sandhya Mehrotra; Rajesh Mehrotra (The Nucleus, 2024)

Modifiable risk factors, oxidative stress markers, and SOD2 rs4880 SNP in coronary artery disease: an association study - Anoop Vijayan; V. Chithra; C. Sandhya (Molecular Biology Reports, 2024)

Silver nanoparticle-induced in vitro flowering in Dendrocalamus strictus (Roxb.) nees and genetic fidelity assessment of regenerants using molecular markers - Bharat Singh Rajput; M. Manokari; Nitin J. Solanki; Dulam Sandhya; Mohammad Faisal; Abdulrahman A. Alatar; Mahipal S. Shekhawat (Molecular Biology Reports, 2024)

Understanding the role of P-type ATPases in regulating pollen fertility and development in pigeonpea - Rishu Jain; Harsha Srivastava; Kuldeep Kumar; Sandhya Sharma; Anandita Singh; Kishor Gaikwad (Molecular Genetics and Genomics, 2024)

Perspective Evaluation of Synthetic Biology Approaches for Effective Mitigation of Heavy Metal Pollution - Sandhya Mishra; Anju Patel; Pankaj Bhatt; Shaohua Chen; Pankaj Kumar Srivastava (Reviews of Environmental Contamination and Toxicology, 2024)

Evolutionary diversity of CXCL16-CXCR6: Convergent substitutions and recurrent gene loss in sauropsids - Buddhabhushan Girish Salve; Sandhya Sharma; Nagarjun Vijay (Immunogenetics, 2024)

“Efficient novel fungal-enriched biochar formulation for hexavalent chromium bioremediation” - Priya Dubey; Aditi Roy; Sandhya Mishra; Mariya Naseem; Alvina Farooqui; Anju Patel; Poonam C. Singh; Pankaj Kumar Srivastava (Journal of Environmental Management, 2024)

A comprehensive study of source apportionment, spatial distribution, and health risks assessment of heavy metal(loid)s in the surface soils of a semi-arid mining region in Matehuala, Mexico - Arnab Saha; Bhaskar Sen Gupta; Sandhya Patidar; Jejanny Lucero Hernández-Martínez; Francisco Martín-Romero; Diana Meza-Figueroa; Nadia Martínez-Villegas (Environmental Research, 2024)

Climatic Oscillations and Dynastic Trends: A Multiproxy analysis of the past two millennia in the Indian Subcontinent - Anjali Trivedi; Shailesh Agrawal; Anupam Sharma; Sheikh Nawaz Ali; M.C. Manoj; Anupam Nag; Sandhya Misra; Masud Kawsar (CATENA, 2024)

Removal of chlorimuron-ethyl from the environment: The significance of microbial degradation and its molecular mechanism - Haoran Song; Wen-Juan Chen; Shao-Fang Chen; Xixian Zhu; Sandhya Mishra; Mohamed A. Ghorab; Pankaj Bhatt; Shaohua Chen (Chemosphere, 2024)

A review on ubiquitin ligases: Orchestrators of plant resilience in adversity - Sandhya Suranjika; Preeti Barla; Namisha Sharma; Nrisingha Dey (Plant Science, 2024)

A kinetic modelling approach to explore mechanism of Cr(VI) detoxification by a novel strain Pseudochrobactrum saccharolyticum NBRI-CRB 13 using response surface methodology - Sandhya Mishra; Priya Dubey; Mariya Naseem; Saloni Rishi; Anju Patel; Pankaj Kumar Srivastava (World Journal of Microbiology and Biotechnology, 2024)

Acute Administration of HIV-1 Tat Protein Drives Glutamatergic Alterations in a Rodent Model of HIV-Associated Neurocognitive Disorders - Brenna C. Duffy; Kirsten M. King; Binod Nepal; Michael R. Nonnemacher; Sandhya Kortagere (Molecular Neurobiology, 2024)
HIV-1-associated neurocognitive disorders (HAND) are a major comorbidity of HIV-1 infection, marked by impairment of executive function varying in severity. HAND affects nearly half of people living with HIV (PLWH), with mild forms predominating since the use of anti-retroviral therapies (ART). The HIV-1 transactivator of transcription (Tat) protein is found in the cerebrospinal fluid of patients adherent to ART, and its administration or expression in animals causes cognitive symptoms. Studies of Tat interaction with the N -methyl- D -aspartate receptor (NMDAR) suggest that glutamate toxicity contributes to Tat-induced impairments. To identify changes in regional glutamatergic circuitry underlying cognitive impairment, we injected recombinant Tat86 or saline to medial prefrontal cortex (mPFC) of male Sprague–Dawley rats. Rats were assessed with behavioral tasks that involve intact functioning of mPFC including the novel object recognition (NOR), spatial object recognition (SOR), and temporal order (TO) tasks at 1 and 2 postoperative weeks. Following testing, mPFC tissue was collected and analyzed by RT-PCR. Results showed Tat86 in mPFC-induced impairment in SOR, and upregulation of Grin1 and Grin2a transcripts. To further understand the mechanism of Tat toxicity, we assessed the effects of full-length Tat101 on gene expression in mPFC by RNA sequencing. The results of RNAseq suggest that glutamatergic effects of Tat86 are maintained with Tat101, as Grin2a was upregulated in Tat101-injected tissue, among other differentially expressed genes. Spatial learning and memory impairment and Grin2a upregulation suggest that exposure to Tat protein drives adaptation in mPFC, altering the function of circuitry supporting spatial learning and memory.

Metformin augments major cytoplasmic organization except for spindle organization in oocytes cultured under hyperglycemic and hyperlipidemic conditions: An in vitro study - Amrutha Nedumbrakkad Kunnath; Shravani Kanakadas Parker; Daphne Norma Crasta; Jyolsna Ponnaratta Kunhiraman; Vanishree Vasave Madhvacharya; Sandhya Kumari; Guruprasad Nayak; R. Vani Lakshmi; Prashanth Kumar Modi; Thottethodi Subrahmanya Keshava Prasad; Anujith Kumar; Ayush Khandelwal; et al. (Toxicology and Applied Pharmacology, 2024)

Industrial symbiosis and eco-industrial transformation opportunities for environmental protection in Nigeria - Abubakar M. Bilyaminu; Eldon R. Rene; Ashok Pandey; Sandhya Babel; Quinnetta Blessing Clement; Anina James; Hector Garcia Hernandez (Sustainable Production and Consumption, 2024)

Modulating elasticity of heat-set soy protein-curdlan gels by small phenolic acids - Pui Yeu Phoon; Amanda Xin Yi Sng; Nikolai Yakovlev; Su Hui Lim; Choy Eng Nge; Gomathy Sandhya Subramanian; Sergey Gorelik; Yoganathan Kanagasundaram; Maxim V. Kiryukhin (Food Hydrocolloids, 2024)

Elucidating the degradation mechanisms of perfluorooctanoic acid and perfluorooctane sulfonate in various environmental matrices: a review of green degradation pathways - Feiyu Chen; Yi Zhou; Liping Wang; Pengfei Wang; Tianyue Wang; Balasubramani Ravindran; Sandhya Mishra; Shaohua Chen; Xiuming Cui; Ye Yang; Wenping Zhang (Environmental Geochemistry and Health, 2024)

Recent Development in Nanoparticle-Assisted Microbial Fuel Cell for Enhanced Reduction of Chromium - G. Vijay Samuel; Nibedita Dey; R. Govindarajan; Kuppusamy Sathishkumar; Muthusamy Govarthanan; J. Sakthidasan; J. Sandhya; Lakshmi Sundeep (Current Microbiology, 2024)

Micro-Raman Spectroscopy Explains the Population-Scale Heterogeneity in Lipid Profile in Chlamydomonas reinhardtii Cultivated Under Single-Stage and Two-Stage Salt Stress - Shubhangi Pandey; Sandhya Mishra; G. Archana; Debjani Bagchi (BioEnergy Research, 2024)

An in vitro model of adipose tissue-associated macrophages - Karishma Bhatia; Sandhya Tiwari; Vikas Kumar Gupta; Neerav M Sapariya; Sanjeev K Upadhyay (Journal of Biosciences, 2024)

Unveiling the abundance and potential impacts of microplastic contamination in commercial organic fertilizers/compost produced from different solid waste - Hewawasam Udumullage Erangi Imasha; Sandhya Babel (Environmental Science and Pollution Research, 2024)

Valorization of Spent Mushroom Substrate (SMS) as a sustainable approach to remediation of xenobiotic compounds in groundwater - A comprehensive review - Garima Gupta; Sandhya Maurya; Prabhat Nath Jha; Puneet Singh Chauhan (Groundwater for Sustainable Development, 2024)

The N-region sequence context impacts the chloroplast import efficiency of multi-TMD protein - Namitha Nayak; Rajesh Mehrotra; Sandhya Mehrotra (Plant Molecular Biology, 2024)

Comparison of Relative Activity versus Relative Expression Factors (RAF versus REF) in Predicting Glucuronidation Mediated Drug Clearance Using Recombinant UGTs - Sandhya Subash; Deepak Ahire; Mitesh Patel; Sahil Shaikh; Dilip Kumar Singh; Sujal Deshmukh; Bhagwat Prasad (Pharmaceutical Research, 2024)

Assessing the potential of C-phycocyanin as a natural colorant for non-alcoholic carbonated beverages - Tonmoy Ghosh; Ismail Rawat; Kiran Bala; Sandhya Mishra; Faizal Bux (Journal of Applied Phycology, 2024)
The multibillion-dollar carbonated beverage industry is currently facing questions from health-conscious consumers over negative health effects of such beverages. Decreasing consumption trends have forced companies to look for healthier choices for their products. C-phycocyanin CPC, a bright blue cyanobacterial pigment with anti-oxidant and other health benefits has been proposed as a candidate in edible drinks. We found that CPC is stable in a wide pH and temperature regime. Reaction kinetics for 12 weeks at 4 °C in non-alcoholic carbonated beverages (B1-B4) showed that B3 (sweetened, ~30 % degradation) best preserved CPC integrity while B1 (non-sweetened, ~87 % degradation) was ineffective. Other beverages (sweetened) could preserve ~ 49 % CPC integrity. Behnajady-Modirshahla-Ghanbary and first order kinetic models explained CPC degradation with and without preservative (sucrose), respectively. The ’consume-by’ times suggest possible refrigeration from ~ 13 hours to 27 days for various CPC-containing beverages. Results suggest CPC could be filter-sterilized and added to non-alcoholic beverages before being packaged in cans or tetra packs to avoid light exposure. Graphical abstract

Screening wild Brassica species against Alternaria brassicicola (Schw.) Wiltsh for breeding Alternaria leaf spot resistance in Brassica vegetables - Shrawan Singh; Sushma Sagar; Mahesh Rao; Sandhya Saroha; Pooja Garg; Lakshman Prasad (Genetic Resources and Crop Evolution, 2024)

Plant cryopreservation: a molecular perspective - Era Vaidya Malhotra; Sangita Bansal; Sandhya Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Proteomic Characterization of Human Placenta: Insights into Potential Therapeutic Applications for Osteoarthritis - Jithu Jerin James; K. V. Sandhya; K. N. Sridhar; S. Sudarson; B. V. Basavaraj; S. Bharath (AAPS PharmSciTech, 2024)

Tapetum-specific expression of cysteine protease induces male sterility in tomato - Phanikanth Jogam; Pandarinath Savitikadi; Dulam Sandhya; Raghu Ellendula; Venkataiah Peddaboina; Venkateswar Rao Allini; Sadanandam Abbagani (Plant Gene, 2024)

Unraveling the mechanism of iodate adsorption by anthocyanin-rich fruit waste as green adsorbents for Applications of radioactive iodine remediation in water environment - Jakkapon Phanthuwongpakdee; Sandhya Babel (Environmental Research, 2024)

Identification of superior haplotypes for flowering time in pigeonpea through candidate gene-based association study of a diverse minicore collection - Kuldeep Kumar; Anita Kumari; Kumar Durgesh; Amitha Mithra Sevanthi; Sandhya Sharma; Nagendra Kumar Singh; Kishor Gaikwad (Plant Cell Reports, 2024)

Sclerotinia sclerotiorum causing white mould on potato in Mauritius - Sandhya Devi Takooree; Hudaa Neetoo; Vijayanti Mala Ranghoo-Sanmukhiya (Indian Phytopathology, 2024)

DNA methylation profiling of labial salivary gland tissues revealed hypomethylation of B-cell-related genes in primary Sjögren’s syndrome - Jayakanthan Kabeerdoss; Prabavathi Devarajalu; Pulukool Sandhya (Immunologic Research, 2024)

Studies on the Production of Budded Nursery Plants in Stool Beds of ‘Rubira’ Peach (Prunus persica [Linnaeus] Batsch) - Preetika Verma; Naveen Chand Sharma; Pramod Verma; Uday Sharma; Sandhya Thakur (Applied Fruit Science, 2024)

A systematic appraisal of ecological niche modelling in the context of phytodiversity conservation - G. Sandhya Kiran; Pankajkumar C. Prajapati; Agradeep Mohanta (Environment, Development and Sustainability, 2024)

Insights in the removal of micropollutants using Fe0+Au0@BN heterojunction: A synergistic in the photo-Fenton-like system - Lalruatkima Ralte; Himangshu Dihingia; Sandhya Pathak; Lalmalsawmdawngliani; Diwakar Tiwari (Groundwater for Sustainable Development, 2024)

Introducing reverse Multi Influencing Factor technique in DRASTIC model for groundwater vulnerability assessment - Sandhya Ganwer; Manish Kumar Sinha; Amit Prakash Multaniya; Nikhil Ghodichore (Groundwater for Sustainable Development, 2024)

Microplastic Pollution in High Population Density Zones of Selected Rivers from Southeast Asia - Anh Tuan Ta; Sandhya Babel; Loan Thi Phuong Nguyen; Emenda Sembiring (Bulletin of Environmental Contamination and Toxicology, 2024)

Optimization of xylanase production by Bacillus sp. MCC2212 under solid-state fermentation using response surface methodology - Ruchika Siwach; Sandhya Sharma; Azmat Ali Khan; Amit Kumar; Sharad Agrawal (Biocatalysis and Agricultural Biotechnology, 2024)

Monitoring genetic transformation with RUBY visible reporter in Nicotiana tabaccum L. - Phanikanth Jogam; Vaishnavi Anumula; Dulam Sandhya; M. Manokari; Ajay Kumar Venkatapuram; V. Mohan Murali Achary; Mahipal S. Shekhawat; Venkataiah Peddaboina; Venkateswar Rao Allini (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Glucagon-Like Peptide-1 Receptor Agonist Cases Reported to United States Poison Centers, 2017–2022 - Christopher E. Gaw; Hannah L. Hays; Cydney A. Kemp; Sandhya Kistamgari; Henry A. Spiller; Natalie I. Rine; Allison L. Rhodes; Motao Zhu; Gary A. Smith (Journal of Medical Toxicology, 2024)
Introduction Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are a class of medications for management of diabetes and obesity. The objective of this study is to characterize the epidemiology of GLP-1RA cases reported to US poison centers. Methods We analyzed cases involving a GLP-1RA reported to the National Poison Data System during 2017–2022. Results There were 5,713 single-substance exposure cases reported to US poison centers involving a GLP-1RA. Most cases were among females (71.3%) and attributable to therapeutic errors (79.9%). More than one-fifth (22.4%) of cases were evaluated in a healthcare facility, including 0.9% admitted to a critical care unit and 4.1% admitted to a non-critical care unit. Serious medical outcomes were described in 6.2% of cases, including one fatality. The rate of cases per one million US population increased from 1.16 in 2017 to 3.49 in 2021, followed by a rapid increase of 80.9% to 6.32 in 2022. Trends for rates of serious medical outcomes and admissions to a healthcare facility showed similar patterns with 129.9% and 95.8% increases, respectively, from 2021 to 2022. Conclusions Most GLP-1RA cases reported to US poison centers were associated with no or minimal effects and did not require referral for medical treatment; however, a notable minority of individuals experienced a serious medical outcome or healthcare facility admission. The rate of reported cases increased during the study period, including an 80.9% increase from 2021 to 2022. Opportunities exist to improve provider and patient awareness of the adverse effects of these medications.

Hydrogen and biodiesel production from food waste: a review - Julkipli Julkipli; Sandhya Babel; Abubakar M. Bilyaminu; Eldon R. Rene (Environmental Chemistry Letters, 2024)

Contamination risk assessment and distribution of rare trace metal(loid)s in surface soil of Cerrito Blanco, Mexico using various contamination indices - Arnab Saha; Bhaskar Sen Gupta; Sandhya Patidar; Nadia Martínez-Villegas (Total Environment Advances, 2024)

Enhanced performance of novel microbial desalination cell using sago effluent as an anolyte: A response surface optimization approach - Sandhya Prakash; Samsudeen Naina Mohamed; Siddanth S.G; Kalaichelvi Ponnusamy (Journal of Water Process Engineering, 2024)

Bioelectricity recovery through isolation and removal of nitrogen from wastewater by shortcut nitrification-denitrification in a coupled microbial fuel cell system - Hoang Dung Nguyen; Sandhya Babel (Fuel, 2024)

Silver doped barium titanate nanoparticles for enhanced visible light photocatalytic degradation of dyes - A. Bhava; U. Sandhya Shenoy; D. Krishna Bhat (Environmental Pollution, 2024)

Occurrence of F-Specific Bacteriophages in Untreated and Treated Wastewaters in Mumbai - Smita Menon; Hima Wani; Dipen Desai; Zarine Bhathena; Nishith Desai; Sandhya Shrivastava (Indian Journal of Microbiology, 2024)

Microplastic interactions in the agroecosystems: methodological advances and limitations in quantifying microplastics from agricultural soil - Pazhamthavalathil Anil Athulya; Yojana Waychal; Andres Rodriguez-Seijo; Sandhya Devalla; C. George Priya Doss; Natarajan Chandrasekaran (Environmental Geochemistry and Health, 2024)

Trend Analysis for Different Types of Aerosols in Conjugation with Temperatures for the Indian Region During the Post-monsoon Season (1980–2019) - Harsh Yadav; Manu Mehta; Shruti Jain; Sandhya Singh; Srishti Bhandari; Seema Nihalani (Aerosol Science and Engineering, 2024)

Preparation of heterogeneous cation exchange membrane and its contributions in enhancing the removal of Ni2+ by capacitive deionization system - Thong Nguyen Tan; Sandhya Babel; Tanujjal Bora; Paiboon Sreearunothai; Kritapas Laohhasurayotin (Chemosphere, 2024)

Multifunctional characteristics of biosynthesized CoFe2O4@Ag nanocomposite by photocatalytic, antibacterial and cytotoxic applications - Sandhya Punyasamudram; Reddy Prasad Puthalapattu; Ayyappa Bathinapatla; Ravikumar Mulpuri; Suvardhan Kanchi; Putta Venkata Nagendra Kumar (Chemosphere, 2024)

Separation and enrichment of tricolor phosphors in waste phosphors through liquid–liquid–powder extraction method and its benefit evaluation for recovery - Li Pang Wang; Jun Ming Hou; Yan Jhang Chen; Bu Ching Tseng; Sandhya Babel (Minerals Engineering, 2024)

Bioactive activity and safety analysis of Monascus red biopigment - Vishu Chaudhary; Priya Katyal; Jaspreet Kaur; Surekha Bhatia; Sandhya Singh; Anuj Kumar Poonia; Anil Kumar Puniya; António Raposo; Sunghoon Yoo; Heesup Han; Hmidan A. Alturki; Anil Kumar (Food Bioscience, 2024)

Microplastic contamination in Thai vinegar crabs (Episesarma mederi), giant mudskippers (Periophthalmodon schlosseri), and their surrounding environment from the Bang Pu mangrove forests, Samut Prakan province, Thailand - Rungpilin Jittalerk; Sandhya Babel (Marine Pollution Bulletin, 2024)

Comparative transcriptome analysis of two contrasting genotypes provides new insights into the drought response mechanism in pigeon pea (Cajanus cajan L. Millsp.) - Suman Pahal; Harsha Srivastava; Swati Saxena; Kishor U. Tribhuvan; Tanvi Kaila; Sandhya Sharma; Sapna Grewal; Nagendra K. Singh; Kishor Gaikwad (Genes & Genomics, 2024)

Spectral mixture analysis of AVIRIS-NG data for grouping plant functional types - Ramandeep Kaur M. Malhi; G. Sandhya Kiran; Prashant K. Srivastava; Bimal K. Bhattacharya; Agradeep Mohanta (Advances in Space Research, 2024)

Efficient extraction and analysis of precious metals with a conducting polymer modified magnetic sorbent material - Abiral Poudel; Sandhya Adhikari; Timnit Y. Asfaha; Joseph G. Lawrence; Manjula M. Kandage; Michal Marszewski; Jon R. Kirchhoff (Resources, Conservation and Recycling, 2023)

Microplastics contamination in the green mussels (Perna viridis) cultured for human consumption in Thailand - Hewawasam Udumullage Erangi Imasha; Sandhya Babel (Regional Studies in Marine Science, 2023)

Unravelling the key contribution of a modified zinc oxide nanostructures on activated carbon cloth material for removal of Cu2+ in different configurations of capacitive deionization system - Thong Nguyen Tan; Sandhya Babel (Journal of Water Process Engineering, 2023)

Efficacy of a neoteric tungsten and phosphorous co-doped TiO2 nano photocatalyst: Studies on bifunctionality in abatement of dye pollutant and microbes - M.L.V. Prasanna Chippada; B.B.V. Sailaja; T. Siva Rao; Gorli Divya; Genji Jaishree; Sandhya Rani Nayak (Environmental Nanotechnology, Monitoring & Management, 2023)

Transformer network for data imputation in electricity demand data - Ashkan Lotfipoor; Sandhya Patidar; David P. Jenkins (Energy and Buildings, 2023)

Marine molluscs of India-a review on their diversity and distribution - Sandhya Leeda D’Souza; K. Bhasker Shenoy (Journal of Coastal Conservation, 2023)

Kisspeptin modulation of nonapeptide and cytochrome P450 aromatase mRNA expression in the brain and ovary of the catfish Heteropneustes fossilis: in vivo and in vitro studies - Radha Chaube; Sandhya Sharma; Keerikkattil Joy (Fish Physiology and Biochemistry, 2023)

Micropropagation and assessment of genetic homogeneity of regenerants by ISSR and SCoT markers in Solena amplexicaulis (Lam.) Gandhi—a threatened medicinal cucurbit - Thirupathi Koppula; Dulam Sandhya; Gulab Khan Rohela; Saritha Kommidi; Mustafa Mohammed (In Vitro Cellular & Developmental Biology - Plant, 2023)

Body size determines multitrophic soil microbiota community assembly associated with soil and plant attributes in a tropical seasonal rainforest - Wenting Wang; Zhenhua Sun; Sandhya Mishra; Shangwen Xia; Luxiang Lin; Xiaodong Yang (Molecular Ecology, 2023)
To understand soil biodiversity we need to know how soil communities are assembled. However, the relationship between soil community assembly and environmental factors, and the linkages between soil microbiota taxonomic groups and their body sizes, remain unexplored in tropical seasonal rainforests. Systematic and stratified random sampling was used to collect 243 soil and organism samples across a 20‐ha plot in a tropical seasonal rainforest in southwestern China. High‐throughput sequencing, variation analysis and principal coordinates of neighbourhood matrices were performed. Soil community composition, spatial distribution and assembly processes based on propagule size (including archaea, bacteria, fungi and nematodes) were investigated. The results showed that: (i) the community assembly of small soil microorganisms (bacteria, fungi) was mostly influenced by stochastic processes while that of larger soil organisms (nematodes) was more deterministic; (ii) the independent effects of habitat (including soil and topographic variables) and its interaction with plant attributes for community structure significantly decreased with increasing body size; and (iii) plant leaf phosphorus directly influenced the spatial distribution of soil‐available phosphorus, which indicates their indirect impact on the assembly of the soil communities. Our data suggest that the assembly of multitrophic soil communities can be explained to some extent by changes in above‐ground plant attributes. This highlights the importance of above‐ and below‐ground linkages in influencing multitrophic soil microbiota community assembly.

Leaf explant based direct and indirect regeneration and SCoT marker assisted genetic fidelity analysis of endemic taxon Corynandra chelidonii var. pallae - Subhash Sirangi; Dulam Sandhya; Gulab Khan Rohela; Mahipal S. Shekhawat; Ragan Ajmeera; Vatsavaya S. Raju (Vegetos, 2023)

Microplastics and heavy metals in a tropical river: Understanding spatial and seasonal trends and developing response strategies using DPSIR framework - Anh Tuan Ta; Sandhya Babel (Science of The Total Environment, 2023)

Imidacloprid and acetamiprid synergistically downregulate spaetzle and myD88 of the Toll pathway in haemocytes of the European honeybee (Apis mellifera) - Sandhya Malladi; Dani Sukkar; Antoine Bonnefoy; Jairo Falla-Angel; Philippe Laval-Gilly (Environmental Toxicology and Pharmacology, 2023)

Technology development and challenges for the transformation of municipal solid waste into sustainable energy production - Tirath Raj; Sandhya Sompura; K. Chandrasekhar; Sushil Kumar Singh; Srinath Pandey; Lalit Kumar Singh; Manish Singh Rajput; Deepak Kumar; Shashi Kant Bhatia; Anil Kumar Patel; Reeta Rani Singhania (Biomass and Bioenergy, 2023)

Hyperspectral Image Classification for Vegetation Detection Using Lightweight Cascaded Deep Convolutional Neural Network - Sandhya Shinde; Hemant Patidar (Journal of the Indian Society of Remote Sensing, 2023)

Bryophytes as Modern Model Plants: An Overview of Their Development, Contributions, and Future Prospects - Sandhya Yadav; Suvajit Basu; Akanksha Srivastava; Subhankar Biswas; Raju Mondal; Vishal Kumar Jha; Sushil Kumar Singh; Yogesh Mishra (Journal of Plant Growth Regulation, 2023)

Novel eco-friendly antimicrobial UV-blocking PBAT/PBS/TiO2 nanocomposite films for improved shelf-life of bananas - Sandhya Alice Varghese; Danaya Phothisarattana; Atcharawan Srisa; Yeyen Laorenza; Lerpong Jarupan; Nattinee Bumbudsanpharoke; Vanee Chonhenchob; Nathdanai Harnkarnsujarit (Food Bioscience, 2023)

Microbial degradation as a powerful weapon in the removal of sulfonylurea herbicides - Qiqi Lei; Jianfeng Zhong; Shao-Fang Chen; Siyi Wu; Yaohua Huang; Peng Guo; Sandhya Mishra; Kalpana Bhatt; Shaohua Chen (Environmental Research, 2023)

Comparative environmental assessment of low and high CaO fly ash in mass concrete mixtures for enhanced sustainability: Impact of fly ash type and transportation - Christian R. Orozco; Somnuk Tangtermsirikul; Takafumi Sugiyama; Sandhya Babel (Environmental Research, 2023)

Sustainable phyco-fabrication of silver nanoparticles using Coelastrella terrestris and their multiple downstream applications - Sunita Choudhary; Geetanjali Kumawat; Manisha Khandelwal; Rama Kanwar Khangarot; Vishambhar Sangela; Mukesh Kumar; Sandhya Deora; Nitish Rai; Vinod Saharan; Harish (Biocatalysis and Agricultural Biotechnology, 2023)

Pharmaceutical aspects of novel CGRP inhibitors used in the prophylaxis and treatment of migraine - Sandhya Jinesh (Inflammopharmacology, 2023)

Regulation of steroid production and key genes in catfish Heteropneustes fossilis using recombinant gonadotropins - Joseph Aizen; Sandhya Sharma; Abigail Elizur; K.P. Joy; Radha Chaube (Fish Physiology and Biochemistry, 2023)

The sources, leaching, remediation, and environmental concerns associated with groundwater salinity - Sandhya Maurya; Preeti Pal; Abhishek Saxena; Dong Zhang (Environmental Science and Pollution Research, 2023)

Direct regeneration from leaf explants and genetic fidelity analysis of regenerates through ISSR markers in Kedrostis foetidissima: a medicinal climber - Kommidi Saritha; Dulam Sandhya; Koppula Thirupathi; Mustafa Mohammed (Vegetos, 2023)

High doses of clethodim-based herbicide GrassOut Max poses reproductive hazard by affecting male reproductive function and early embryogenesis in Swiss albino mice - Reyon Dcunha; Sandhya Kumari; Mohd Altaf Najar; Anjana Aravind; Keerthana Sandesh Suvarna; Ananda Hanumappa; Sadhana P. Mutalik; Srinivas Mutalik; Sneha Guruprasad Kalthur; G.K. Rajanikant; Sazada Siddiqui; Sulaiman Alrumman; et al. (Chemosphere, 2023)

Bioactivity-guided isolation of trypanocidal coumarins and dihydro-pyranochromones from selected Apiaceae plant species - Sandhya R. Krishnan; Adrianna Skiba; Simon Vlad Luca; Laurence Marcourt; Jean-Luc Wolfender; Krystyna Skalicka-Woźniak; Jürg Gertsch (Phytochemistry, 2023)

Biotransformation of banana peel waste into bacterial nanocellulose and its modification for active antimicrobial packaging using polyvinyl alcohol with in-situ generated silver nanoparticles - Hina Khan; Sharad Raghuvanshi; Vaishali Saroha; Sandhya Singh; Waqas N. Baba; Priti Mudgil; Dharm Dutt (Food Packaging and Shelf Life, 2023)

Performance of novel pillared eggshell-bentonite clay bio-composite for enhanced phosphate adsorption from aqueous media - Sandhya Sudhakaran; Harsha Mahadevan; Linsha Fathima S; Krishnan Anoop Krishnan (Groundwater for Sustainable Development, 2023)

Unravelling and enhancing the power recovery and nitrogen removal mechanism from wastewater by isolating input nitrogen in a coupled microbial fuel cell system - Hoang Dung Nguyen; Sandhya Babel (Environmental Research, 2023)

Efficient biodegradation of multiple pyrethroid pesticides by Rhodococcus pyridinivorans strain Y6 and its degradation mechanism - Yaohua Huang; Shao-Fang Chen; Wen-Juan Chen; Xixian Zhu; Sandhya Mishra; Pankaj Bhatt; Shaohua Chen (Chemical Engineering Journal, 2023)

Long-term performance of grid-integrated solar photovoltaic system on institutional buildings in tropical wet and dry climates of India — a practical study - Bhogula Navothna; Sandhya Thotakura (Environmental Science and Pollution Research, 2023)

Performance evaluation of microalgal strains for concurrent production of high-value bio-actives lutein and phytol: A step forward towards the multi-product paradigm - Shreya Sadukha; Apoorva Bhayani; Hemanshi Padariya; Pradipkumar Vaghela; Sandhya Mishra; Arup Ghosh; Ramalingam Dineshkumar (Biocatalysis and Agricultural Biotechnology, 2023)

On drastic change in the relationship between snow cover and Indian monsoon rainfall - M Sandhya; S Sridharan (Journal of Earth System Science, 2023)

Current insights into the microbial degradation of nicosulfuron: Strains, metabolic pathways, and molecular mechanisms - Jianfeng Zhong; Siyi Wu; Wen-Juan Chen; Yaohua Huang; Qiqi Lei; Sandhya Mishra; Pankaj Bhatt; Shaohua Chen (Chemosphere, 2023)

Occurrence and spatial distribution of microplastic contaminated with heavy metals in a tropical river: Effect of land use and population density - Anh Tuan Ta; Sandhya Babel (Marine Pollution Bulletin, 2023)

High-efficiency degradation of methomyl by the novel bacterial consortium MF0904: Performance, structural analysis, metabolic pathways, and environmental bioremediation - Shimei Pang; Ziqiu Lin; Wen-Juan Chen; Shao-Fang Chen; Yaohua Huang; Qiqi Lei; Pankaj Bhatt; Sandhya Mishra; Shaohua Chen; Huishan Wang (Journal of Hazardous Materials, 2023)

Edible oil to powder technologies: Concepts and advances - K. Sandhya; M. Maria Leena; J.A. Moses; C. Anandharamakrishnan (Food Bioscience, 2023)

Biorecognition elements appended gold nanoparticle biosensors for the detection of food-borne pathogens - A review - Sandhya Sadanandan; Meenakshi V. S; Keerthana Ramkumar; Neeraja P. Pillai; Anuvinda P; Sreelekshmi P. J; Devika V; Ramanunni K; Jeevan Sankar R; M.M. Sreejaya (Food Control, 2023)

Editing of TOM1 gene in tobacco using CRISPR/Cas9 confers resistance to Tobacco mosaic virus - Phanikanth Jogam; Dulam Sandhya; Anshu Alok; Venkataiah Peddaboina; Sudhir P. Singh; Sadanandam Abbagani; Baohong Zhang; Venkateswar Rao Allini (Molecular Biology Reports, 2023)

The Phylogenetic Study of the CRISPR-Cas System in Enterobacteriaceae - Simran Krishnakant Kushwaha; Aryahi A. Kumar; Hardik Gupta; Sandhya Amol Marathe (Current Microbiology, 2023)

Genomic survey of high-throughput RNA-Seq data implicates involvement of long intergenic non-coding RNAs (lincRNAs) in cytoplasmic male-sterility and fertility restoration in pigeon pea - Swati Saxena; Antara Das; Tanvi Kaila; G. Ramakrishna; Sandhya Sharma; Kishor Gaikwad (Genes & Genomics, 2023)

Wastewater-Based Epidemiology of SARS-CoV-2: Assessing Prevalence and Correlation with Clinical Cases - Hima Wani; Smita Menon; Dipen Desai; Nishita D’Souza; Zarine Bhathena; Nishith Desai; Joan B. Rose; Sandhya Shrivastava (Food and Environmental Virology, 2023)

Development of immobilized novel fungal consortium for the efficient remediation of cyanide-contaminated wastewaters - Saloni Rishi; Ispreet Kaur; Mariya Naseem; Vivek Kumar Gaur; Sandhya Mishra; Suchi Srivastava; Harvinder Singh Saini; Pankaj Kumar Srivastava (Bioresource Technology, 2023)

Pediatric Suspected Suicides and Nonfatal Suicide Attempts Reported to United States Poison Control Centers Before and During the COVID-19 Pandemic - Hailee R. Ciccotti; Henry A. Spiller; Marcel J. Casavant; Sandhya Kistamgari; Alexandra R. Funk; Gary A. Smith (Journal of Medical Toxicology, 2023)

Intracellular trehalose modulates oxidative responses and dehydrin gene expression in Arabidopsis thaliana (L.) Heynh during dehydration - Akhil Mohanan; Sandhya Gandhi; Noor Al Ain A; Dinakar Challabathula (Brazilian Journal of Botany, 2023)

Recent advances in Surface Plasmon Resonance (SPR) biosensors for food analysis: a review - Nevetha Ravindran; Sandhya Kumar; Yashini M; Rajeshwari S; Mamathi C A; Nirmal Thirunavookarasu S; Sunil C K (Critical Reviews in Food Science and Nutrition, 2023)

Seasonal difference in soil health indicators mediating multidiversity-multifunctionality relationship depends on body size of soil organisms: Evidence from rubber plantation agroforestry system - Wenting Wang; Sandhya Mishra; Xiaodong Yang (Soil Biology and Biochemistry, 2023)

Characterization of the Sediment Bacterial Community Structure and Composition in Najafgarh Lake and Adjoining Dhansa Barrage - Sandhya Bhat; Harbinder Kaur; Priyanka Verma; Pamposh (Indian Journal of Microbiology, 2023)

Answer to “Comments on “Regulation of Paraquat for wheat crop contamination” by Garg, Gupta, S. et al., https://doi.org/10.1007/s11356-022–20,816-8” - Sandhya Gupta; Navneet Kumar Garg; Kapila Shekhawat (Environmental Science and Pollution Research, 2023)

Water stress response on morpho-physiology, biochemical parameters and yield of four different rice cultivars of Manipur - Wangkhem Sandhya Chanu; Kananbala Sarangthem (Vegetos, 2023)

Antimicrobial, antioxidant, cytotoxicity and photocatalytic performance of Co doped ZnO nanoparticles biosynthesized using Annona Muricata leaf extract - P. S. Vindhya; Sandhya Suresh; R. Kunjikannan; V. T. Kavitha (Journal of Environmental Health Science and Engineering, 2023)

Environmental occurrence, toxicity concerns, and biodegradation of neonicotinoid insecticides - Xidong Zhang; Yaohua Huang; Wen-Juan Chen; Siyi Wu; Qiqi Lei; Zhe Zhou; Wenping Zhang; Sandhya Mishra; Pankaj Bhatt; Shaohua Chen (Environmental Research, 2023)

Defect-induced electronic modification and surface reconstruction of catalysts during water oxidation process - Gracita M. Tomboc; Sandhya Venkateshalu; Quang-Tung Ngo; Songa Choi; Bruno G. Pollet; Hangil Lee; Kwangyeol Lee (Chemical Engineering Journal, 2023)

Proteins as fuzzy controllers: Auto tuning a biological fuzzy inference system to predict protein dynamics in complex biological networks - Mohammad Abdallah Alsharaiah; Sandhya Samarasinghe; Don Kulasiri (BioSystems, 2023)

Targeted nano-delivery of chemotherapy via intranasal route suppresses in vivo glioblastoma growth and prolongs survival in the intracranial mouse model - Puja Sandbhor; Jayant Goda; Bhabani Mohanty; Poonam Gera; Sandhya Yadav; Godanjali Chekuri; Pradip Chaudhari; Shilpee Dutt; Rinti Banerjee (Drug Delivery and Translational Research, 2023)

Population genetic research on the Spadenose shark, Scoliodon laticaudus (Chondrichthyes, Carcharhinidae), reveals the presence of two significantly differentiated clades along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; P. U. Zacharia; Shoba J. Kizhakudan; K. V. Akhilesh; Sujitha Thomas; Subal Kumar Roul; M. Muktha; Swati Priyanka Sen; G. B. Purushottama; Shikha Rahangdale; K. K. Bineesh; et al. (Marine Biodiversity, 2023)

Inducible overexpression of cecropin B decreases the susceptibility of the transgenic silkworm, Bombyx mori (Lepidoptera: Bombycidae), to bacteria - Rasalkar Sandhya Yashwant; Dyna Susan Thomas; Chitra Manoharan; Upendra Nongthomba; Vankadara Sivaprasad; Ravikumar Gopalapillai (Applied Entomology and Zoology, 2023)

Ghost fishing capacity of lost experimental gillnets: a preliminary study from Indian waters - Saly N. Thomas; Sandhya Kavitha Mandhir; Harsha Krishnankutty; Mary Baby K. A.; Aishwarya Ghosh K. A. (Environmental Science and Pollution Research, 2023)

Collective computational intelligence in biology – Emergence of memory in somatic tissues - Sandhya Samarasinghe (BioSystems, 2023)

Environmental Characterization of Two Ecologically Distinct Gangetic Oxbow Lakes using Zooplankton Taxonomic Indices Through Comparative Approach for Wetland Monitoring - Suman Kumari; Lianthuamluaia Lianthuamluaia; Uttam Kumar Sarkar; Mishal Puthiyottil; Gunjan Karnatak; Dharmendra Kumar Meena; Sandhya Kavitha Mandhir; Md Abul Hassan; Ashok Kumar Jaiswar; Anil Prakash Sharma; Basanta Kumar Das (Wetlands, 2023)

Exome sequencing and microarray identified a novel large exonic deletion in SYT2 gene in an ultra-rare case with recessive CMS type 7 - C. P. Ravi Kumar; Parag M. Tamhankar; Radhika Manohar; Sheetal Sharda; G. K. Madhavilatha; S. G. Thenral; Sandhya Nair; A. K. Bojamma (Journal of Genetics, 2022)

Spatiotemporal assessment of groundwater quality in the Central Ganga Plain, India, using multivariate statistical tools - Sandhya Maurya; Abhishek Saxena (Environmental Monitoring and Assessment, 2022)

Explicit versus implicit consideration of binding partners in protein–protein complex to elucidate intrinsic dynamics - Bhaskar Dasgupta; Sandhya P. Tiwari (Biophysical Reviews, 2022)

Effect of functional and effective brain connectivity in identifying vowels from articulation imagery procedures - Sandhya Chengaiyan; Kavitha Anandan (Cognitive Processing, 2022)

Optimization of Gibberellic Acid Production in Endophytic Bacillus cereus Using Response Surface Methodology and Its Use as Plant Growth Regulator in Chickpea - Nitin Baliyan; Sandhya Dhiman; Shrivardhan Dheeman; Sandeep Kumar; Naveen Kumar Arora; Dinesh Kumar Maheshwari (Journal of Plant Growth Regulation, 2022)

Regulation of Paraquat for wheat crop contamination - Sandhya Gupta; Navneet Kumar Garg; Kapila Shekhawat (Environmental Science and Pollution Research, 2022)

Development of efficient Agrobacterium rhizogenes-mediated hairy root system in Curcuma longa L. and elicitation driven enhanced production of pharmaceutically important curcuminoids - S. Sandhya; Archana Giri (In Vitro Cellular & Developmental Biology - Plant, 2022)

Influence of southern hemispheric upper troposphere potential vorticity intrusion events on the southwest monsoon rainfall - M Sandhya; S Sridharan (Journal of Earth System Science, 2022)

Formulating Ternary Inclusion Complex of Sorafenib Tosylate Using β-Cyclodextrin and Hydrophilic Polymers: Physicochemical Characterization and In Vitro Assessment - Mahipal Reddy Donthi; Siva Ram Munnangi; Kowthavarapu Venkata Krishna; Sandhya Amol Marathe; Ranendra Narayan Saha; Gautam Singhvi; Sunil Kumar Dubey (AAPS PharmSciTech, 2022)

Bacteriophage cocktails as antibacterial agents in crop protection - Nitin Baliyan; Sandhya Dhiman; Shrivardhan Dheeman; Vineet Kumar Vishnoi; Sandeep Kumar; Dinesh Kumar Maheshwari (Environmental Sustainability, 2022)

An insight into phytic acid biosynthesis and its reduction strategies to improve mineral bioavailability - Sandhya Sharma; Lalitha Hari Dharani AnandKumar; Anshika Tyagi; Mehanthan Muthumilarasan; Kuldeep Kumar; Kishor Gaikwad (The Nucleus, 2022)

Evaluation of the Bioefficacy and Insecticide Compatibility of Entomopathogens for Management of Whitefly (Hemiptera: Aleyrodidae) on Upland Cotton Under Laboratory and Polyhouse Conditions - Satish Kumar Sain; Dilip Monga; Sandhya Kranthi; Neelakanth S. Hiremani; Dipak T. Nagrale; Rishi Kumar; Surender Kumar Verma; Yenumula G. Prasad (Neotropical Entomology, 2022)

Importance of clitellar tissue in the regeneration ability of earthworm Eudrilus eugeniae - Sayan Paul; Subburathinam Balakrishnan; Arun Arumugaperumal; Saranya Lathakumari; Sandhya Soman Syamala; Vijithkumar Vijayan; Selvan Christyraj Jackson Durairaj; Vaithilingaraja Arumugaswami; Sudhakar Sivasubramaniam (Functional & Integrative Genomics, 2022)

Cloning and homologous characterization of geranylgeranyl pyrophosphate synthase (GGPPS) from Withania somnifera revealed alterations in metabolic flux towards gibberellic acid biosynthesis - Yashdeep Srivastava; Sandhya Tripathi; Bhawana Mishra; Neelam S. Sangwan (Planta, 2022)

Advances and prospects in the food applications of pectin hydrogels - Padma Ishwarya S.; Sandhya R.; P. Nisha (Critical Reviews in Food Science and Nutrition, 2022)

Identification, tissue specific expression analysis and functional characterization of arrestin gene (ARRDC) in the earthworm Eudrilus eugeniae: a molecular hypothesis behind worm photoreception - Sayan Paul; Sudalai Mani Dinesh Kumar; Sandhya Soman Syamala; Subburathinam Balakrishnan; Vijithkumar Vijayan; Vaithilingaraja Arumugaswami; Sivasubramaniam Sudhakar (Molecular Biology Reports, 2022)

Pharmaceutical perspective of neuropathic pain management for primary care providers - Sandhya Jinesh; Justin Kullgren; Gollapudi S. Shankar; Rajan Radhakrishnan (Inflammopharmacology, 2022)

Operating temperature prediction and comparison for rooftop PV arrays in coastal climates of India - Sandhya Thotakura; Sri Chandan Kondamudi (Environmental Science and Pollution Research, 2022)

Effect of ACGT motif in spatiotemporal regulation of AtAVT6D, which improves tolerance to osmotic stress and nitrogen-starvation - Pinky Dhatterwal; Sandhya Mehrotra; Anthony J. Miller; Raviprasad Aduri; Rajesh Mehrotra (Plant Molecular Biology, 2022)

Seasonal Changes in the Antioxidative Defence System of a Liverwort Dumortiera hirsuta - Sandhya Yadav; Akanksha Srivastava; Subhankar Biswas; Suvajit Basu; Sushil Kumar Singh; Yogesh Mishra (Journal of Plant Growth Regulation, 2022)

New Record of Fanged Seabream, Sparidentex jamalensis (Perciformes: Sparidae) From Indian Waters - Madathampady Thomas Shilta; Padinhate Purayil Suresh Babu; Pillaru Kandiyil Asokan; Kavungal Vinod; Sandhya Sukumaran; Imelda Joseph; Ramya Abhijith (Thalassas: An International Journal of Marine Sciences, 2022)

Epigenetic regulation and autophagy modulation debilitates insulin resistance associated Alzheimer’s disease condition in rats - Violina Kakoty; Sarathlal K C; Sunil Kumar Dubey; Chih-Hao Yang; Sandhya Amol Marathe; Rajeev Taliyan (Metabolic Brain Disease, 2022)

Performance analysis of Pseudomonas sp. strain SA3 in naphthalene degradation using phytotoxicity and microcosm studies - Sushma Rani Tirkey; Shristi Ram; Madhusree Mitra; Sandhya Mishra (Biodegradation, 2022)

Functional analysis of SCD1 gene involved in pathogenicity of spot blotch disease of wheat causing fungus Bipolaris sorokiniana - Kartar Singh; Rashmi Aggarwal; Praveen Kumar Verma; Sandhya Verma; Sapna Sharma; C. Manjunatha; Manoj Choudhary; Deepika Kulshreshtha; Kirti Rawat (Indian Phytopathology, 2022)

Assessment of molecular genetic diversity of 384 chickpea genotypes and development of core set of 192 genotypes for chickpea improvement programs - Humara Fayaz; Asma Hamid Mir; Sandhya Tyagi; Aijaz A. Wani; Nelofar Jan; Mohammad Yasin; Javid Iqbal Mir; Biswajit Mondal; Mohd Anwar Khan; Reyazul Rouf Mir (Genetic Resources and Crop Evolution, 2022)

Molluscan diversity of coastal Karnataka, India and role of physicochemical parameters on their diversity - Sandhya Leeda D’Souza; Neevan D’Souza; K Bhasker Shenoy (Journal of Coastal Conservation, 2022)

A comprehensive review on leguminous galactomannans: structural analysis, functional properties, biosynthesis process and industrial applications - Priya Sharma; Sandhya Sharma; G. Ramakrishna; Harsha Srivastava; Kishor Gaikwad (Critical Reviews in Food Science and Nutrition, 2022)

Influence of Miscanthus × giganteus and Trifolium repens L. on microflora and PAH-degrading bacteria in contaminated technosol - Laura Wechtler; Sonia Henry; Sandhya Malladi; Antoine Bonnefoy; Jaïro Falla-Angel; Philippe Laval-Gilly (Journal of Soils and Sediments, 2022)

Promoter profiling of Arabidopsis amino acid transporters: clues for improving crops - Pinky Dhatterwal; Sandhya Mehrotra; Anthony J. Miller; Rajesh Mehrotra (Plant Molecular Biology, 2021)

Funding for cancer research by an Indian funding agency, DBT - Sandhya R Shenoy; Bindu Dey (Journal of Biosciences, 2021)

Predominance of genetically diverse ESBL Escherichia coli identified in resistance mapping of Vembanad Lake, the largest fresh-cum-brackishwater lake of India - Murugadas Vaiyapuri; Anna SherinPulithara Sebastian; Iris George; Sandhya Soolamkandath Variem; Radhakrishnan Nair Vasudevan; Joshy Chalil George; Madhusudana Rao Badireddy; Visnuvinayagam Sivam; Shaheer Peeralil; Devi Sanjeev; Muthulakshmi Thandapani; Sheela Albert Moses; et al. (Environmental Science and Pollution Research, 2021)

Bioelectrochemical technology for recovery of silver from contaminated aqueous solution: a review - Ngo Anh Dao Ho; Sandhya Babel (Environmental Science and Pollution Research, 2021)

Genetic determinants of micronutrient traits in graminaceous crops to combat hidden hunger - P. Sushree Shyamli; Sumi Rana; Sandhya Suranjika; Mehanathan Muthamilarasan; Ajay Parida; Manoj Prasad (Theoretical and Applied Genetics, 2021)

Development of marker-free insect resistant transgenic okra (Abelmoschus esculentus L. Moench) expressing the cry1Ac gene and identification of vector backbone-free events - Satish Deole; Sanjeev Padakipatil; S. R. Sandhya; Asaram Nanote; Murlidhar Jadhav; Pankaj Bihani; Srinivas Parimi; Usha Zehr; M. Narendran; Bharat R. Char (Physiology and Molecular Biology of Plants, 2021)

Microplastics Contamination in Commercial Green Mussels from Selected Wet Markets in Thailand - Hewawasam Udumullage Erangi Imasha; Sandhya Babel (Archives of Environmental Contamination and Toxicology, 2021)

Climate change and high-altitude food security: a small-scale study from the Karnali region in Nepal - Sandhya Thapa; Abid Hussain (Climate and Development, 2021)

In vitro activity of reconstituted rubisco enzyme from Gloeobacter violaceus - Gurpreet Kaur Sidhu; Panchsheela Nogia; Vandana Tomar; Rajesh Mehrotra; Sandhya Mehrotra (Journal of Biosciences, 2021)

Enterobacter hormaechei (MF957335) enhanced yield, disease and salinity tolerance in tomato - Bablesh Ranawat; Sandhya Mishra; Aneesha Singh (Archives of Microbiology, 2021)

Sedimentological responses to coastal dynamics along the Thane District, North Maharashtra, West Coast of India - Sridhar D. Iyer; A. R. Gujar; V. Sanil Kumar; D. K. Naik; S. S. Gaonkar; Sandhya Naik; Pooja Shirodkar; F. Badesab; R. A. A. Luis (Sustainable Water Resources Management, 2021)

Mitochondrial COI based genetic diversity and phylogeographic structure of whitefly Bemisia tabaci (Gennadius) on cotton in India - Prabhulinga T; Sandhya Kranthi; Raghavendra K P; Rishi Kumar; Ruchika Suke; Shilpa Chawla; Keshav Raj Kranthi (International Journal of Tropical Insect Science, 2021)

The signals of selective constraints on the mitochondrial non-coding control region: insights from comparative mitogenomics of Clupeoid fishes - Wilson Sebastian; Sandhya Sukumaran; A. Gopalakrishnan (Genetica, 2021)

ZnO nanoparticles for photodegradation of humic acid in water - Sandhya Babel; Putri A. Sekartaji; Hanggara Sudrajat (Environmental Science and Pollution Research, 2021)

Seaweed-based biostimulant improves photosynthesis and effectively enhances growth and biofuel potential of a green microalga Chlorella variabilis - Himanshu Sati; Kaumeel Chokshi; Rajapitamahuni Soundarya; Arup Ghosh; Sandhya Mishra (Aquaculture International, 2021)

Monitoring Water Quality in Lien Son Irrigation System of Vietnam and Identification of Potential Pollution Sources by Using Multivariate Analysis - Bui Quoc Lap; Nguyen Hoai Nam; Bui Thi Kim Anh; Trinh Thi Thuy Linh; Le Xuan Quang; Vu Duc Toan; Bui Thi Thanh Hang; Sandhya Babel; Thi-Thu-Hong Phan (Water, Air, & Soil Pollution, 2021)

Molecular characterization of SlATG18f in response to Tomato leaf curl New Delhi virus infection in tomato and development of a CAPS marker for leaf curl disease tolerance - Ashish Prasad; Gunaseelen Hari-Gowthem; Mehanathan Muthamilarasan; Zakir Hussain; Pawan Kumar Yadav; Sandhya Tripathi; Manoj Prasad (Theoretical and Applied Genetics, 2021)

Comparative transcriptome analyses revealed different heat stress responses in pigeonpea (Cajanus cajan) and its crop wild relatives - G. Ramakrishna; Parampreet Kaur; Anupam Singh; Sunishtha S. Yadav; Sandhya Sharma; N. K. Singh; Kishor Gaikwad (Plant Cell Reports, 2021)

Determining the presence of glyphosate and glyphosate-tolerant events in maize and soybean food products in South Africa - Christopher D. Viljoen; B. J. Koortzen; Sandhya Sreenivasan Tantuan (Food Additives & Contaminants Part B-Surveillance, 2021)

Exploring the Neuroprotective Potential of Rosiglitazone Embedded Nanocarrier System on Streptozotocin Induced Mice Model of Alzheimer’s Disease - Sarathlal K C; Violina Kakoty; Sandhya Marathe; Deepak Chitkara; Rajeev Taliyan (Neurotoxicity Research, 2021)

Enterobacter hormaechei as Plant Growth-Promoting Bacteria for Improvement in Lycopersicum esculentum - Bablesh Ranawat; Pooja Bachani; Aneesha Singh; Sandhya Mishra (Current Microbiology, 2021)

Food selectivity and reproductive biology of small indigenous fish Indian river shad, Gudusia chapra (Hamilton, 1822) in a large tropical reservoir - Suman Kumari; Uttam Kumar Sarkar; Gunjan Karnatak; Sandhya Kavitha Mandhir; Lianthuamluaia Lianthuamluaia; Vikash Kumar; Debabrata Panda; Mishal Puthiyottil; Basanta Kumar Das (Environmental Science and Pollution Research, 2021)

Phycosphere associated bacteria; a prospective source of bioactive compounds - Sandhya Soolamkandath Variem; Vijayan Koyadan Kizhakkedath (Biologia, 2021)

The transcriptome of anterior regeneration in earthworm Eudrilus eugeniae - Sayan Paul; Subburathinam Balakrishnan; Arun Arumugaperumal; Saranya Lathakumari; Sandhya Soman Syamala; Vaithilingaraja Arumugaswami; Sudhakar Sivasubramaniam (Molecular Biology Reports, 2021)

Application of a Two-Analyte Integrated Population Pharmacokinetic Model to Evaluate the Impact of Intrinsic and Extrinsic Factors on the Pharmacokinetics of Polatuzumab Vedotin in Patients with Non-Hodgkin Lymphoma - Dan Lu; Tong Lu; Rong Shi; Leonid Gibiansky; Priya Agarwal; Colby S. Shemesh; Randall C. Dere; Uzor Ogbu; Jamie Hirata; Pascal Chanu; Sandhya Girish; Jin Yan Jin; et al. (Pharmaceutical Research, 2020)
Purpose The established two-analyte integrated population pharmacokinetic model was applied to assess the impact of intrinsic/extrinsic factors on the pharmacokinetics (PK) of polatuzumab vedotin (pola) in patients with non-Hodgkin lymphoma (NHL) following bodyweight-based dosing. Methods Model simulations based on individual empirical Bayes estimates were used to evaluate the impact of intrinsic/extrinsic factors as patient subgroups on Cycle 6 exposures. Intrinsic factors included bodyweight, age, sex, hepatic and renal functions. Extrinsic factors included rituximab/obinutuzumab or bendamustine combination with pola and manufacturing process. The predicted impact on exposures along with the established exposure-response relationships were used to assess clinical relevance. Results No clinically meaningful differences in Cycle 6 pola exposures were found for the following subgroups: bodyweight 100–146 kg versus 38–<100 kg, age ≥ 65 years versus <65 years, female versus male, mild hepatic impairment versus normal, mild-to-moderate renal impairment versus normal. Co-administration of rituximab/obinutuzumab or bendamustine, and change in the pola manufacturing process, also had no meaningful impact on PK. Conclusions In patients with NHL, bodyweight-based dosing is adequate, and no further dose adjustment is recommended for the heavier subgroup (100–146 kg). In addition, no dose adjustments are recommended for other subgroups based on intrinsic/extrinsic factors evaluated.

Can Dominant Canopy Species Leaf Litter Determine Soil Nutrient Heterogeneity? A Case Study in a Tropical Rainforest in Southwest China - Anjana J. Atapattu; Shang-wen Xia; Min Cao; Wen-fu Zhang; Sandhya Mishra; Xiaodong Yang (Journal of Soil Science and Plant Nutrition, 2020)

In vivo evaluation of microbial cocktail of microalgae-associated bacteria in larval rearing from zoea I to mysis I of the Indian white shrimp, Penaeus indicus - S. V. Sandhya; K. P. Sandeep; K. K. Vijayan (Journal of Applied Phycology, 2020)

Decoding social behaviors in a glycerol dependent bacterial consortium during Reactive Blue 28 degradation - Sandhya Nanjani; Khushboo Rawal; Hareshkumar Keharia (Brazilian Journal of Microbiology, 2020)

Study on the SFRP4 gene polymorphism and expression in prostate cancer - AISHWARYA NATARAJAN; SHAILE SUDHA BANDLA; MOHAN DAMODARAN; SANDHYA SUNDARAM; VETTRISELVI VENKATESAN (Journal of Genetics, 2020)

Evidence for the loss of plasminogen receptor KT gene in chicken - Sandhya Sharma; Sagar Sharad Shinde; Lokdeep Teekas; Nagarjun Vijay (Immunogenetics, 2020)

Buffalo dung-inhabiting bacteria enhance the nutrient enrichment of soil and proximate contents of Foeniculum vulgare Mill - Sandhya Dhiman; Nitin Baliyan; Dinesh Kumar Maheshwari (Archives of Microbiology, 2020)

Effect of Aging and 5-Fluorouracil Treatment on Bone Marrow Stem Cell Dynamics - Ranita Ganguly; Sandhya Anand; Siddhanath Metkari; Deepa Bhartiya (Stem Cell Reviews and Reports, 2020)

Altered Biology of Testicular VSELs and SSCs by Neonatal Endocrine Disruption Results in Defective Spermatogenesis, Reduced Fertility and Tumor Initiation in Adult Mice - Ankita Kaushik; Sandhya Anand; Deepa Bhartiya (Stem Cell Reviews and Reports, 2020)

Population genetic structure of the oceanic whitetip shark, Carcharhinus longimanus, along the Indian coast - S. Sreelekshmi; Sandhya Sukumaran; T. G. Kishor; Wilson Sebastian; A. Gopalakrishnan (Marine Biodiversity, 2020)

Improving the performance of conventional base isolation systems by an external variable negative stiffness device under near-fault and long-period ground motions - Sandhya Nepal; Masato Saitoh (Earthquake Engineering and Engineering Vibration, 2020)

Status of Hilsa Fishery in Hooghly-Bhagirathi River System and Associated Coastal Waters of Northern Bay of Bengal - A. M. Sajina; V. R. Suresh; K. M. Sandhya; J. Mukherjee; R. K. Manna; B. K. Behera; R. Samanta; T. Maity; S. K. Banik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Recombinant expression of sericin-cecropin fusion protein and its functional activity - Dyna Susan Thomas; Chitra Manoharan; Sandhya Rasalkar; Rakesh Kumar Mishra; Ravikumar Gopalapillai (Biotechnology Letters, 2020)

Differential Reprogramming of Defense Network in Capsicum annum L. Plants Against Colletotrichum truncatum Infection by Phyllospheric and Rhizospheric Trichoderma Strains - Amrita Saxena; Sandhya Mishra; Shatrupa Ray; Richa Raghuwanshi; Harikesh Bahadur Singh (Journal of Plant Growth Regulation, 2020)

Characterization of the Whole Mitogenome of Largehead Hairtail Trichiurus lepturus (Trichiuridae): Insights into Special Characteristics - Lakshmi P. Mukundan; Sandhya Sukumaran; Wilson Sebastian; A. Gopalakrishnan (Biochemical Genetics, 2020)

Virus-Specific T Cells for the Treatment of Malignancies—Then, Now, and the Future - Sandhya Sharma; Wingchi K Leung; Helen E Heslop (Current Stem Cell Reports, 2020)

Antibacterial and biofilm inhibition activity of biofabricated silver nanoparticles against Xanthomonas oryzae pv. oryzae causing blight disease of rice instigates disease suppression - Sandhya Mishra; Xiaodong Yang; Shatrupa Ray; Leonardo Fernandes Fraceto; H. B. Singh (World Journal of Microbiology and Biotechnology, 2020)

Molecular analyses reveal a lack of genetic structuring in the scalloped hammerhead shark, Sphyrna lewini (Griffith & Smith, 1834) along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; Lakshmi P. Mukundan; Muktha Menon; K. V. Akhilesh; P. U. Zacharia; A. Gopalakrishnan (Marine Biodiversity, 2020)

Synergetic use of in situ and hyperspectral data for mapping species diversity and above ground biomass in Shoolpaneshwar Wildlife Sanctuary, Gujarat - Ramandeep Kaur M. Malhi; Akash Anand; Ashwini N. Mudaliar; Prem C. Pandey; Prashant K. Srivastava; G. Sandhya Kiran (Tropical Ecology, 2020)

Rational Design, Synthesis, and In Vitro Neuroprotective Evaluation of Novel Glitazones for PGC-1α Activation via PPAR-γ: a New Therapeutic Strategy for Neurodegenerative Disorders - Antony Justin; Subhankar Mandal; P. Prabitha; S. Dhivya; S. Yuvaraj; Pradeep Kabadi; Satheesh John Sekhar; C. H. Sandhya; Ashish D. Wadhwani; Selvaraj Divakar; Jeyabalan Jeyaram Bharathi; Priya Durai; et al. (Neurotoxicity Research, 2020)

Modeling the effect of sanitation in a human habitat to control the spread of bacterial diseases - J. B. Shukla; Ram Naresh; Sandhya Rani Verma; Manju Agarwal (Modeling Earth Systems and Environment, 2020)

Identification of vowels in consonant–vowel–consonant words from speech imagery based EEG signals - Sandhya Chengaiyan; Anandha Sree Retnapandian; Kavitha Anandan (Cognitive Neurodynamics, 2020)

Development and Investigation of Vitamin C-Enriched Adapalene-Loaded Transfersome Gel: a Collegial Approach for the Treatment of Acne Vulgaris - Sandhya Vasanth; Akhilesh Dubey; Ravi G.S.; Shaila A. Lewis; Vivek M. Ghate; Sally A. El-Zahaby; Srinivas Hebbar (AAPS PharmSciTech, 2020)

Characterization of the olfactory system of the giant honey bee, Apis dorsata - Sandhya Mogily; Meenakshi VijayKumar; Sunil Kumar Sethy; Joby Joseph (Cell and Tissue Research, 2020)

Application of potassium-solubilising Proteus mirabilis MG738216 inhabiting cattle dung in improving nutrient use efficiency of Foeniculum vulgare Mill. - Sandhya Dhiman; Ramesh Chand Dubey; Nitin Baliyan; Sandeep Kumar; Dinesh Kumar Maheshwari (Environmental Sustainability, 2019)

Comparative Response of Cardiomyocyte ZIPs and ZnTs to Extracellular Zinc and TPEN - Sandhya Thokala; Vijaya Lakshmi Bodiga; Madhukar Rao Kudle; Sreedhar Bodiga (Biological Trace Element Research, 2019)

Creating a global database “Nanomaterials in the soil environment”: future need for the terrestrial ecosystem - Sandhya Mishra; Harikesh Bahadur Singh; Xiaodong Yang (Energy, Ecology and Environment, 2019)

New Record of Ariomma brevimanum (Klunzinger, 1884) (Perciformes: Ariommatidae) from Indian Waters - Subal Kumar Roul; Rajan Kumar; Shikha Rahangdale; Suraj Kumar Pradhan; Sandhya Sukumaran; Prathibha Rohit (Thalassas: An International Journal of Marine Sciences, 2019)

Actinomycin-Producing Endophytic Streptomyces parvulus Associated with Root of Aloe vera and Optimization of Conditions for Antibiotic Production - Sandhya Chandrakar; Ashwini Kumar Gupta (Probiotics and Antimicrobial Proteins, 2019)

Fertilizer-induced fluxes dominate annual N2O emissions from a nitrogen-rich temperate fen rewetted for paludiculture - Tanka P. Kandel; Sandhya Karki; Lars Elsgaard; Poul Erik Lærke (Nutrient Cycling in Agroecosystems, 2019)

Validation of QTL for grain weight using MAS-derived pairs of NILs in bread wheat (Triticum aestivum L.) - Supriya Kumari; Reyazul Rouf Mir; Sandhya Tyagi; Harindra Singh Balyan; Pushpendra Kumar Gupta (Journal of Plant Biochemistry and Biotechnology, 2019)

Signatures of Relaxed Selection in the CYP8B1 Gene of Birds and Mammals - Sagar Sharad Shinde; Lokdeep Teekas; Sandhya Sharma; Nagarjun Vijay (Journal of Molecular Evolution, 2019)

Insecticidal activity of botanical oils and other neem-based derivatives against whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) on cotton - Rishi Kumar; Sandhya Kranthi; V. S. Nagrare; D. Monga; Keshav Raj Kranthi; Naveen Rao; Amarpreet Singh (International Journal of Tropical Insect Science, 2019)

Studies on the use of sodium polyacrylate (SPA) for low-salt animal skin preservation - Venkatakrishnan Balasubramanian; Brindha Velappan; Sandhya Kurvilla Vijayan; Hepzibah Jabamani; Vedaraman Nagarajan; John Sundar Victor; Suresha P. Ranganath; Manohar V. Badiger; Velappan Kandukalpatti Chinnaraj; Muralidharan Chellappa (Environmental Science and Pollution Research, 2019)

Symbiotic association among marine microalgae and bacterial flora: a study with special reference to commercially important Isochrysis galbana culture - S. V. Sandhya; K. K. Vijayan (Journal of Applied Phycology, 2019)

Contemporary and historic patterns of intraspecific diversity in Indian anchovy, Stolephorus indicus, from Indian peninsular waters - Sandhya Sukumaran; Wilson Sebastian; K. X. Francis; A. Gopalakrishnan (Genetica, 2019)

Myocyte Enhancer Factor 2c Regulates Dendritic Complexity and Connectivity of Cerebellar Purkinje Cells - Sandhya Prakash Kamath; Albert I. Chen (Molecular Neurobiology, 2019)

Studies on the Production of Broad Spectrum Antimicrobial Compound Polypeptide (Actinomycins) and Lipopeptide (Fengycin) from Streptomyces sp. K-R1 Associated with Root of Abutilon indicum against Multidrug Resistant Human Pathogens - Sandhya Chandrakar; Ashwini Kumar Gupta (International Journal of Peptide Research and Therapeutics, 2019)

Fish assemblage structure and spatial gradients of diversity in a large tropical reservoir, Panchet in the Ganges basin, India - Kavitha Mandhir Sandhya; Lianthuamluaia Lianthuamluaia; Gunjan Karnatak; Uttam Kumar Sarkar; Suman Kumari; Puthiyottil Mishal; Vikash Kumar; Debabrata Panda; Yousuf Ali; Bablu Kumar Naskar (Environmental Science and Pollution Research, 2019)

Comparative RNA editing profile of mitochondrial transcripts in cytoplasmic male sterile and fertile pigeonpea reveal significant changes at the protein level - Tanvi Kaila; Swati Saxena; G. Ramakrishna; Anshika Tyagi; Kishor U. Tribhuvan; Harsha Srivastava; Sandhya; Ashok Chaudhury; Nagendra Kumar Singh; Kishor Gaikwad (Molecular Biology Reports, 2019)

Isolation and phylogenetic identification of heterotrophic thraustochytrids from mangrove habitats along the southwest coast of India and prospecting their PUFA accumulation - K. V. Jaseera; P. Kaladharan; K. K. Vijayan; S. V. Sandhya; M. Leo Antony; M. A. Pradeep (Journal of Applied Phycology, 2019)

Understanding spatial and temporal patterns of fish diversity and assemblage structure vis-a-vis environmental parameters in a tropical Indian reservoir - Lianthuamluaia Lianthuamluaia; Puthiyottil Mishal; Debabrata Panda; Uttam Kumar Sarkar; Vikash Kumar; Kavitha Mandhir Sandhya; Gunjan Karnatak; Suman Kumari; Asit Kumar Bera; Subrata Das; Yusuf Ali (Environmental Science and Pollution Research, 2019)

Co-cultivation of siderophore-producing bacteria Idiomarina loihiensis RS14 with Chlorella variabilis ATCC 12198, evaluation of micro-algal growth, lipid, and protein content under iron starvation - Soundarya Rajapitamahuni; Pooja Bachani; Raj Kumar Sardar; Sandhya Mishra (Journal of Applied Phycology, 2019)

A climatological study of the spatio-temporal variability of land surface temperature and vegetation cover of Vadodara district of Gujarat using satellite data - Neha Nandkeolyar; G. Sandhya Kiran (International Journal of Remote Sensing, 2019)

Spectral Modelling on the Characteristics of High Frequency Tail in Shallow Water Wave Spectra at Coastal Puducherry, East Coast of India - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2019)

Event-Related Potentials in Response to Facial Affect Recognition in Patients with Schizophrenia - G. Sandhya; H. P. Prakash; K. R Nayak; R. V. Behere; P. R. Bhandary; A. S. Chinmay (Neurophysiology, 2019)

Population Status and Diurnal Behaviour of the Indian Flying Fox Pteropus giganteus (Brünnich, 1782) in Kathmandu Valley, Nepal - Sandhya Manandhar; Sanjan Thapa; Tej Kumar Shrestha; Rabindra Jyakhwo; Wendy Wright; Achyut Aryal (Proceedings of the Zoological Society, 2018)

Correction to: Application of a Novel ‘Make and Test in Parallel’ Strategy to Investigate the Effect of Formulation on the Pharmacokinetics of GDC-0810 in Healthy Subjects - Sravanthi Cheeti; Hao Helen Hou; Eric Nelson; Helen Walker; Buyun Chen; Roland Morley; Mary Gates; Luna Musib; Sandhya Girish; Srikumar Sahasranaman; Lichuan Liu (Pharmaceutical Research, 2018)

Application of a Novel ‘Make and Test in Parallel’ Strategy to Investigate the Effect of Formulation on the Pharmacokinetics of GDC-0810 in Healthy Subjects - Sravanthi Cheeti; Hao Helen Hou; Eric Nelson; Helen Walker; Buyun Chen; Roland Morley; Mary Gates; Luna Musib; Sandhya Girish; Srikumar Sahasranaman; Lichuan Liu (Pharmaceutical Research, 2018)

Isolation and characterization of Aquaporin 1 (AQP1), sodium/potassium-transporting ATPase subunit alpha-1 (Na/K-ATPase α1), Heat Shock Protein 90 (HSP90), Heat Shock Cognate 71 (HSC71), Osmotic Stress Transcription Factor 1 (OSTF1) and Transcription Factor II B (TFIIB) genes from a euryhaline fish, Etroplus suratensis - Wilson Sebastian; Sandhya Sukumaran; P. U. Zacharia; A. Gopalakrishnan (Molecular Biology Reports, 2018)

The complete mitochondrial genome and phylogeny of Indian oil sardine, Sardinella longiceps and Goldstripe Sardinella, Sardinella gibbosa from the Indian Ocean - Wilson Sebastian; Sandhya Sukumaran; P. U. Zacharia; A. Gopalakrishnan (Conservation Genetics Resources, 2018)

pH as a proxy for estimating plant-available Si? A case study in rice fields in Karnataka (South India) - Jean-Dominique Meunier; Kollalu Sandhya; Nagabovanalli B. Prakash; Daniel Borschneck; Philippe Dussouillez (Plant and Soil, 2018)

Studies on the growth and mortality of Indian River shad, Gudusia chapra (Hamilton, 1822) from Panchet reservoir, India - Suman Kumari; Uttam Kumar Sarkar; Sandhya Kavitha Mandhir; Lianthuamluaia Lianthuamluaia; Debabrata Panda; Sushanta Kumar Chakraborty; Gunjan Karnatak; Vikash Kumar; Mishal Puthiyottil (Environmental Science and Pollution Research, 2018)

Sacred Groves: Treasure House for Macrolichen Diversity in Kumaun Himalaya - Yogesh Joshi; Shashi Upadhyay; Sandhya Shukla; Kapil Bisht; Krishna Chandra; Manish Tripathi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Tied up: Does altering phosphoinositide-mediated membrane trafficking influence neurodegenerative disease phenotypes? - Sravanthi S. P. Nadiminti; Madhushree Kamak; Sandhya P. Koushika (Journal of Genetics, 2018)

High Frequency Tail Characteristics in the Coastal Waters off Gopalpur, Northwest Bay of Bengal: A Nearshore Modelling Study - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2018)

A Pharmacometric Analysis of Patient-Reported Outcomes in Breast Cancer Patients Through Item Response Theory - Emilie Schindler; Lena E. Friberg; Bertram L. Lum; Bei Wang; Angelica Quartino; Chunze Li; Sandhya Girish; Jin Y. Jin; Mats O. Karlsson (Pharmaceutical Research, 2018)

Re-description of the longtail butterfly ray, Gymnura poecilura (Shaw, 1804) (Gymnuridae: Myliobatiformes) from Bay of Bengal with a neotype designation - M. Muktha; K. V. Akhilesh; S. Sandhya; F. Jasmin; M. A. Jishnudev; Shoba Joe Kizhakudan (Marine Biodiversity, 2018)

Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview - U. K. Sarkar; K. M. Sandhya; P. Mishal; G. Karnatak; S. Kumari; P. Panikkar; R. Palaniswamy; M. Karthikeyan; S. Sibina Mol; T. T. Paul; V. L. Ramya; D. S. K. Rao; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

C-Phycoerythrin as a Colorimetric and Fluorometric Probe for the Sensitive, Selective and Quantitative Detection of Cu2+ in Aqueous Samples - Tonmoy Ghosh; Apeksha Vyas; Khushbu Bhayani; Sandhya Mishra (Journal of Fluorescence, 2018)

Origin of silica in rice plants and contribution of diatom Earth fertilization: insights from isotopic Si mass balance in a paddy field - Jean Riotte; Kollalu Sandhya; Nagabovanalli B. Prakash; Stéphane Audry; Thomas Zambardi; Jérôme Chmeleff; Sriramulu Buvaneshwari; Jean-Dominique Meunier (Plant and Soil, 2018)

Preclinical evaluation of the Aurora kinase inhibitors AMG 900, AZD1152-HQPA, and MK-5108 on SW-872 and 93T449 human liposarcoma cells - Sandhya Noronha; Lauren A. C. Alt; Taylor E. Scimeca; Omran Zarou; Justyna Obrzut; Brian Zanotti; Elizabeth A. Hayward; Akhil Pillai; Shubha Mathur; Joseph Rojas; Ribhi Salamah; Nalini Chandar; et al. (In Vitro Cellular & Developmental Biology - Animal, 2018)

Isolation and expression analysis of defensin gene and its promoter from Brassica juncea - Sandhya Rawat; Sajad Ali; N. N. Chamil Nayankantha; N. Chandrashekar; Bhabatosh Mittra; Anita Grover (Journal of Plant Diseases and Protection, 2017)

Platform model describing pharmacokinetic properties of vc-MMAE antibody–drug conjugates - Matts Kågedal; Leonid Gibiansky; Jian Xu; Xin Wang; Divya Samineni; Shang-Chiung Chen; Dan Lu; Priya Agarwal; Bei Wang; Ola Saad; Neelima Koppada; Bernard M. Fine; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Identification and comparative analysis of Brassica juncea pathogenesis-related genes in response to hormonal, biotic and abiotic stresses - Sajad Ali; Zahoor Ahmad Mir; Anshika Tyagi; Javaid A. Bhat; Narayanappa Chandrashekar; Pradeep Kumar Papolu; Sandhya Rawat; Anita Grover (Acta Physiologiae Plantarum, 2017)

Regulatory components of carbon concentrating mechanisms in aquatic unicellular photosynthetic organisms - Vandana Tomar; Gurpreet Kaur Sidhu; Panchsheela Nogia; Rajesh Mehrotra; Sandhya Mehrotra (Plant Cell Reports, 2017)

Hydroponic Screening of Fast-growing Tree Species for Lead Phytoremediation Potential - Jiraporn Yongpisanphop; Sandhya Babel; Maleeya Kruatrachue; Prayad Pokethitiyook (Bulletin of Environmental Contamination and Toxicology, 2017)

Antibiotic Potential of Endophytic Actinomycetes of Medicinal Herbs Against Human Pathogenic Bacteria - Sandhya Chandrakar; A. K. Gupta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Factors influencing silver recovery and power generation in bio-electrochemical reactors - Ngo Anh Dao Ho; Sandhya Babel; Korakot Sombatmankhong (Environmental Science and Pollution Research, 2017)

Zinc Dyshomeostasis in Cardiomyocytes after Acute Hypoxia/Reoxygenation - Vijaya Lakshmi Bodiga; Sandhya Thokala; Sita Mahalaxmi Kovur; Sreedhar Bodiga (Biological Trace Element Research, 2017)

Genetic population structure of Indian oil sardine, Sardinella longiceps assessed using microsatellite markers - Wilson Sebastian; Sandhya Sukumaran; P. U. Zacharia; A. Gopalakrishnan (Conservation Genetics, 2017)

Chromosome Complements of Isodon (Family: Lamiaceae–Subfamily: Nepetoideae): Trends in Karyotype Evolution - Sandhya Vincent Neelamkavil; John E. Thoppil (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Withania coagulans tryptophan decarboxylase gene cloning, heterologous expression, and catalytic characteristics of the recombinant enzyme - Jyoti Singh Jadaun; Neelam Singh Sangwan; Lokesh Kumar Narnoliya; Sandhya Tripathi; Rajender Singh Sangwan (Protoplasma, 2017)

Preparation, characterization, and bio-efficacy evaluation of controlled release carbendazim-loaded polymeric nanoparticles - Sandhya; Sandeep Kumar; Dinesh Kumar; Neeraj Dilbaghi (Environmental Science and Pollution Research, 2017)

Release of silver nanoparticles from fabrics during the course of sequential washing - Pawena Limpiteeprakan; Sandhya Babel; Jenyuk Lohwacharin; Satoshi Takizawa (Environmental Science and Pollution Research, 2016)

Growth medium standardization and thermotolerance study of the freshwater microalga Acutodesmus dimorphus—a potential strain for biofuel production - Kaumeel Chokshi; Imran Pancha; Rahulkumar Maurya; Chetan Paliwal; Tonmoy Ghosh; Arup Ghosh; Sandhya Mishra (Journal of Applied Phycology, 2016)

Cyanobacterial Pigments as Natural Anti-Hyperglycemic Agents: An In vitro Study - Tonmoy Ghosh; Khushbu Bhayani; Chetan Paliwal; Rahulkumar Maurya; Kaumeel Chokshi; Imran Pancha; Sandhya Mishra (Frontiers in Marine Science, 2016)

RETRACTED ARTICLE: Overexpression of thaumatin gene confers enhanced resistance to Alternaria brassicae and tolerance to salinity and drought in transgenic Brassica juncea (L.) Czern - Alkesh Hada; Sandhya Rawat; Veda Krishnan; Monica Jolly; Theboral Jeevaraj; Markandan Manickavasagam; Andy Ganapathi; Archana Sachdev; Anita Grover (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Erratum to: De-oiled neem cake as potential bio-additive for low-salt raw skin preservation: a process for salinity reduction in tanneries - N. Vedaraman; K. V. Sandhya; V. Brindha; A. Tamil Selvi; K. C. Velappan; V. John Sundar; J. Kanagaraj; C. Muralidharan (International Journal of Environmental Science and Technology, 2016)

De-oiled neem cake as potential bio-additive for low-salt raw skin preservation: a process for salinity reduction in tanneries - N. Vedaraman; K. V. Sandhya; V. Brindha; A. Tamil Selvi; K. C. Velappan; V. John Sundar; J. Kanagaraj; C. Muralidharan (International Journal of Environmental Science and Technology, 2016)

Rapid photocatalytic degradation of the recalcitrant dye amaranth by highly active N-WO3 - Hanggara Sudrajat; Sandhya Babel (Environmental Chemistry Letters, 2016)

Comparison and mechanism of photocatalytic activities of N-ZnO and N-ZrO2 for the degradation of rhodamine 6G - Hanggara Sudrajat; Sandhya Babel (Environmental Science and Pollution Research, 2016)

Mangrove root: adaptations and ecological importance - Sandhya Srikanth; Shawn Kaihekulani Yamauchi Lum; Zhong Chen (Trees, 2016)

Fluorescence Quenching Property of C-Phycocyanin from Spirulina platensis and its Binding Efficacy with Viable Cell Components - Meenakshi B. Paswan; Meghna M. Chudasama; Madhusree Mitra; Khushbu Bhayani; Basil George; Shruti Chatterjee; Sandhya Mishra (Journal of Fluorescence, 2016)

Role of habitat and great oxidation event on the occurrence of three multisubunit inorganic carbon-uptake systems in cyanobacteria - VANDANA TOMAR; GURPREET KAUR SIDHU; PANCHSHEELA NOGIA; RAJESH MEHROTRA; SANDHYA MEHROTRA (Journal of Genetics, 2016)

Light and auxin responsive cytochrome P450s from Withania somnifera Dunal: cloning, expression and molecular modelling of two pairs of homologue genes with differential regulation - Sudhakar Srivastava; Rajender Singh Sangwan; Sandhya Tripathi; Bhawana Mishra; L. K. Narnoliya; L. N. Misra; Neelam S. Sangwan (Protoplasma, 2015)

Analysis of SARAL/AltiKa Wind and Wave over Indian Ocean and its Real-time Application in Wave Forecasting System at ISRO - Suchandra Aich Bhowmick; Ruchi Modi; K. G. Sandhya; M. Seemanth; T. M. Balakrishnan Nair; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

Does size matter? Comparative population genetics of two butterflies with different wingspans - Sandhya Sekar; K. Praveen Karanth (Organisms Diversity & Evolution, 2015)

Development of a new CMS system in pigeonpea utilizing crosses with Cajanus lanceolatus (WV Fitgz) van der Maesen - Sandhya Srikanth; Rachit K. Saxena; M. V. Rao; Rajeev K. Varshney; Nalini Mallikarjuna (Euphytica, 2015)

AECHL-1, a novel triterpenoid, targets tumor neo-vasculature and impairs the endothelial cell cytoskeleton - Aparajita Dasgupta; Mithila A. Sawant; Manish S. Lavhale; Lakshmi-Surekha Krishnapati; Surendra Ghaskadbi; Sandhya L. Sitasawad (Angiogenesis, 2015)

Semi-mechanistic Multiple-Analyte Pharmacokinetic Model for an Antibody-Drug-Conjugate in Cynomolgus Monkeys - Dan Lu; Jin Yan Jin; Sandhya Girish; Priya Agarwal; Dongwei Li; Saileta Prabhu; Randall C. Dere; Ola M. Saad; Denise Nazzal; Neelima Koppada; Saroja Ramanujan; Chee M. Ng (Pharmaceutical Research, 2015)

Pharmaceutical aspects of anti-inflammatory TNF-blocking drugs - Sandhya Jinesh (Inflammopharmacology, 2015)

Evaluating microbe-plant interactions and varietal differences for enhancing biocontrol efficacy in root rot disease challenged cotton crop - Santosh Babu; Ngangom Bidyarani; Preeti Chopra; Dilip Monga; Rishi Kumar; Radha Prasanna; Sandhya Kranthi; Anil Kumar Saxena (European Journal of Plant Pathology, 2015)

Study of Trace Elements in Liver Cirrhosis Patients and Their Role in Prognosis of Disease - Vijaylaxmi Nangliya; Anjali Sharma; Dharamveer Yadav; Shyam Sunder; Sandeep Nijhawan; Sandhya Mishra (Biological Trace Element Research, 2015)

Diurnal variations of the low-level jet over peninsular India during the onset of Asian summer monsoon - Sandhya K. Nair; Thara V. Prabha; N. Purushothaman; S. Sijikumar; S. Muralidharan; N. V. P. Kirankumar; D. B. Subrahamanyam; T. J. Anurose; S. S. Prijith; K. V. S. Namboodiri (Theoretical and Applied Climatology, 2015)

Full GHG balance of a drained fen peatland cropped to spring barley and reed canary grass using comparative assessment of CO2 fluxes - Sandhya Karki; Lars Elsgaard; Tanka P. Kandel; Poul Erik Lærke (Environmental Monitoring and Assessment, 2015)

Comparative atom-based 3D QSAR study of 3-nitro-1H-1,2,4-triazole-based aliphatic and aromatic amines analogs for its anti-trypanosomal activities - Suresh Kumar; Ritesh Agrawal; Sandhya Bawa (Medicinal Chemistry Research, 2015)

The adenylyl cyclase Rv2212 modifies the proteome and infectivity of Mycobacterium bovis BCG - César Pedroza-Roldán; Michel de Jesús Aceves-Sánchez; Anisha Zaveri; Claudia Charles-Niño; Darwin Eduardo Elizondo-Quiroga; Rodolfo Hernández-Gutiérrez; Kirk Allen; Sandhya S. Visweswariah; Mario Alberto Flores-Valdez (Folia Microbiologica, 2015)

Dominance of cyanobacterial and cryptophytic assemblage correlated to CDOM at heavy metal contamination sites of Gujarat, India - Shailesh Kumar Patidar; Kaumeel Chokshi; Basil George; Sourish Bhattacharya; Sandhya Mishra (Environmental Monitoring and Assessment, 2015)

Candidate gene analysis for determinacy in pigeonpea (Cajanus spp.) - Reyazul Rouf Mir; Himabindu Kudapa; Sandhya Srikanth; Rachit K. Saxena; Ashutosh Sharma; Sarwar Azam; Kulbhushan Saxena; R. Varma Penmetsa; Rajeev K. Varshney (Theoretical and Applied Genetics, 2014)

Sequestration of CO2 by halotolerant algae - Udhaya Ramkrishnan; Benedict Bruno; Sandhya Swaminathan (Journal of Environmental Health Science and Engineering, 2014)
The potential of halotolerant algae isolated from natural resources was used to study CO 2 fixation and algal lipid production. Biological fixation of CO 2 in photobioreactor in presence of salinity is exploited. The CO 2 concentration 1060 ppm gave the highest biomass yield (700 mg dry wt/l), the highest total lipid content (10.33%) with 80% of CO 2 removal.

Carbon concentrating mechanisms: in rescue of Rubisco inefficiency - Gurpreet Kaur Sidhu; Rajesh Mehrotra; Sandhya Mehrotra (Acta Physiologiae Plantarum, 2014)

Optimum Calcium Concentration: A Crucial Factor in Regulating Sperm Motility In Vitro - Arpita Bhoumik; Sudipta Saha; Gopal Chandra Majumder; Sandhya Rekha Dungdung (Cell Biochemistry and Biophysics, 2014)

Mitigation of greenhouse gas emissions from reed canary grass in paludiculture: effect of groundwater level - Sandhya Karki; Lars Elsgaard; Joachim Audet; Poul Erik Lærke (Plant and Soil, 2014)

Differential gene expression profile in Pseudomonas putida NBRIC19-treated wheat (Triticum aestivum) plants subjected to biotic stress of Parthenium hysterophorus - Sandhya Mishra; Suchi Srivastava; Chandra Shekhar Nautiyal (Molecular Biology Reports, 2014)

Inorganic nanovectors for nucleic acid delivery - Sandhya Pranatharthiharan; Mitesh D. Patel; Anisha A. D’Souza; Padma V. Devarajan (Drug Delivery and Translational Research, 2013)

Reduced cell wall degradation plays a role in cow dung-mediated management of wilt complex disease of chickpea - Chandra Shekhar Nautiyal; Suchi Srivastava; Sandhya Mishra; Mehar Hasan Asif; Puneet Singh Chauhan; Poonam C. Singh; Pravendra Nath (Biology and Fertility of Soils, 2013)

Biomass Yield and Greenhouse Gas Emissions from a Drained Fen Peatland Cultivated with Reed Canary Grass under Different Harvest and Fertilizer Regimes - Tanka P. Kandel; Lars Elsgaard; Sandhya Karki; Poul E. Lærke (BioEnergy Research, 2013)

C-mitotic effect of aqueous extracts of Isodon coetsa (Buch.-Ham. ex D. Don) Kudo (Lamiaceae) - Sandhya Vincent Neelamkavil; John Ernest Thoppil (The Nucleus, 2013)

Elucidation of binding mechanism and identification of binding site for an anti HIV drug, stavudine on human blood proteins - B. Sandhya; Ashwini H. Hegde; J. Seetharamappa (Molecular Biology Reports, 2013)

Estimation of variables explaining urbanization concomitant with land-use change: a spatial approach - G. Sandhya Kiran; Usha B. Joshi (International Journal of Remote Sensing, 2013)

A megacity in a changing climate: the case of Kolkata - Susmita Dasgupta; Asvani K. Gosain; Sandhya Rao; Subhendu Roy; Maria Sarraf (Climatic Change, 2013)

Production of polyhydroxyalkanoates from Ralstonia eutropha using paddy straw as cheap substrate - M. Sandhya; J. Aravind; P. Kanmani (International Journal of Environmental Science and Technology, 2013)

A Study of Carotid Atherosclerosis in Patients with Non-alcoholic Fatty Liver Disease - Sandhya Mishra; Dharamveer Yadav; Monika Gupta; Hemant Mishra; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2013)

Establishment of Reference Interval for Liver Specific Biochemical Parameters in Apparently Healthy North Indian Population - Dharamveer Yadav; Sandhya Mishra; Monika Gupta; P. J. John; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2013)

Pseudomonas putida NBRIC19 provides protection to neighboring plant diversity from invasive weed Parthenium hysterophorus L. by altering soil microbial community - Sandhya Mishra; Puneet Singh Chauhan; Anil Kumar Goel; Ram Sanmukh Upadhyay; Chandra Shekhar Nautiyal (Acta Physiologiae Plantarum, 2012)

Genotype Frequencies of Drug-Metabolizing Enzymes Responsible for Purine and Pyrimidine Antagonists in a Healthy Asian-Indian Population - Sandhya N. Iyer; Ashwini V. Tilak; Manjari S. Mukherjee; Rekha S. Singhal (Biochemical Genetics, 2012)

Interaction of fishes with pathogenic micro-organisms and application of phages for their control: a review - Swapnil G. Sanmukh; Dilip B. Meshram; Waman N. Paunikar; Sandhya Swaminathan (Reviews in Fish Biology and Fisheries, 2012)

Impact of continental meteorology and atmospheric circulation in the modulation of Aerosol Optical Depth over the Arabian Sea - SANDHYA K NAIR; S SIJIKUMAR; S S PRIJITH (Journal of Earth System Science, 2012)

Contribution of GPR30 for 1,25 dihydroxyvitamin D3 protection in EAE - Sandhya Subramanian; Lisa M. Miller; Marjorie R. Grafe; Arthur A. Vandenbark; Halina Offner (Metabolic Brain Disease, 2012)

Differences between Cajanus cajan (L.) Millspaugh and C. cajanifolius (Haines) van der Maesen, the progenitor species of pigeonpea - Nalini Mallikarjuna; Kulbushan Saxena; Jhansi Lakshmi; Rajeev Varshney; Sandhya Srikanth; Deepak Jadhav (Genetic Resources and Crop Evolution, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Impact of Chronic Lead Exposure on Selected Biological Markers - Ambica P. Jangid; P. J. John; D. Yadav; Sandhya Mishra; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2012)

Evaluation of binding and thermodynamic characteristics of interactions between a citrus flavonoid hesperitin with protein and effects of metal ions on binding - Ashwini H. Hegde; B. Sandhya; J. Seetharamappa (Molecular Biology Reports, 2011)

Design and synthesis of 2-chloroquinoline derivatives as non-azoles antimycotic agents - Suresh Kumar; Sandhya Bawa; Sushma Drabu; Bibhu P. Panda (Medicinal Chemistry Research, 2011)

Cajanus platycarpus (Benth.) Maesen as the donor of new pigeonpea cytoplasmic male sterile (CMS) system - Nalini Mallikarjuna; Deepak R. Jadhav; Sandhya Srikanth; Kulbhushan B. Saxena (Euphytica, 2011)

Bioaccumulation of Metals in the Edible Catfish Heteropneustes fossilis (Bloch) Exposed to Coal Mine Effluent Generated at Northern Coalfield Limited, Singrauli, India - Sandhya Bharti; Tarun Kumar Banerjee (Bulletin of Environmental Contamination and Toxicology, 2011)

Isotopic labeling of the heme cofactor in cytochrome p450 and other heme proteins - David Bryson; Pek-Lang Lim; Alin Lawson; Sandhya Manjunath; Gregory M. Raner (Biotechnology Letters, 2011)

AAPS Workshop Report: Strategies to Address Therapeutic Protein–Drug Interactions during Clinical Development - Sandhya Girish; Steven W Martin; Mark C Peterson; Lei K. Zhang; Hong Zhao; Joseph Balthasar; Raymond Evers; Honghui Zhou; Min Zhu; Lewis Klunk; Chao Han; Eva Gil Berglund; et al. (The AAPS Journal, 2011)

Update on the Chemopreventive Effects of Ginger and its Phytochemicals - Manjeshwar Shrinath Baliga; Raghavendra Haniadka; Manisha Maria Pereira; Jason Jerome D’Souza; Princy Louis Pallaty; Harshith P. Bhat; Sandhya Popuri (Critical Reviews in Food Science and Nutrition, 2011)

Biodegradability studies of polyhydroxyalkanoate (PHA) film produced by a marine bacteria using Jatropha biodiesel byproduct as a substrate - Anupama Shrivastav; Sanjiv K. Mishra; Imran Pancha; Deepti Jain; Sourish Bhattacharya; Sheetal Patel; Sandhya Mishra (World Journal of Microbiology and Biotechnology, 2011)

Sustained expression of circulating human alpha-1 antitrypsin reduces inflammation, increases CD4+FoxP3+ Treg cell population and prevents signs of experimental autoimmune encephalomyelitis in mice - Sandhya Subramanian; Galit Shahaf; Eyal Ozeri; Lisa M. Miller; Arthur A. Vandenbark; Eli C. Lewis; Halina Offner (Metabolic Brain Disease, 2011)

Role of microorganisms in adaptation of agriculture crops to abiotic stresses - Minakshi Grover; Sk. Z. Ali; V. Sandhya; Abdul Rasul; B. Venkateswarlu (World Journal of Microbiology and Biotechnology, 2011)

Designer promoter: an artwork of cis engineering - Rajesh Mehrotra; Gauri Gupta; Riccha Sethi; Purva Bhalothia; Narayan Kumar; Sandhya Mehrotra (Plant Molecular Biology, 2011)

Requirements of Slm proteins for proper eisosome organization, endocytic trafficking and recycling in the yeast Saccharomyces cerevisiae - Chitra Kamble; Sandhya Jain; Erin Murphy; Kyoungtae Kim (Journal of Biosciences, 2011)

Reference Intervals of Certain Liver Specific Biochemical Analytes in Indian Population - Dharmveer Yadav; Sandhya Mishra; Monika Gupta; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2011)

Effect of osmotic stress on plant growth promoting Pseudomonas spp. - V. Sandhya; Sk. Z. Ali; B. Venkateswarlu; Gopal Reddy; Minakshi Grover (Archives of Microbiology, 2010)

Differential outcomes from metabolic ratios in the identification of CYP2D6 phenotypes–focus on venlafaxine and O-desmethylvenlafaxine - Mani Kandasamy; P. Srinivas; Kala Subramaniam; Sandhya Ravi; James John; Radha Shekar; Nuggehally Srinivas; Saral Thangam (European Journal of Clinical Pharmacology, 2010)

Cloning and characterization of truncated cry1Ab gene from a new indigenous isolate of Bacillus thuringiensis - Sandhya Darsi; G. Divya Prakash; V. Udayasuriyan (Biotechnology Letters, 2010)

Antioxidant and anti-stress compounds improve regrowth of cryopreserved Rubus shoot tips - Esther E. Uchendu; Magfrat Muminova; Sandhya Gupta; Barbara M. Reed (In Vitro Cellular & Developmental Biology - Plant, 2010)

Recombinant TCR Ligand Reverses Clinical Signs and CNS Damage of EAE Induced by Recombinant Human MOG - Sushmita Sinha; Sandhya Subramanian; Ashley Emerson-Webber; Maren Lindner; Gregory G. Burrows; Marjorie Grafe; Christopher Linington; Arthur A. Vandenbark; Claude C. A. Bernard; Halina Offner (Journal of Neuroimmune Pharmacology, 2010)

Receptor guanylyl cyclase C (GC-C): regulation and signal transduction - Nirmalya Basu; Najla Arshad; Sandhya S. Visweswariah (Molecular and Cellular Biochemistry, 2010)

Agrobacterium-Mediated Transformation of cry1Ac Gene into Shoot-Tip Meristem of Diploid Cotton Gossypium arboreum cv. RG8 and Regeneration of Transgenic Plants - S. B. Nandeshwar; Sandhya Moghe; P. K. Chakrabarty; M. K. Deshattiwar; Keshav Kranthi; P. Anandkumar; C. D. Mayee; B. M. Khadi (Plant Molecular Biology Reporter, 2009)

Antidiabetic effects of scoparic acid D isolated from Scoparia dulcis in rats with streptozotocin-induced diabetes - Muniappan Latha; Leelavinothan Pari; Kunga Mohan Ramkumar; Palanisamy Rajaguru; Thangaraj Suresh; Thangavel Dhanabal; Sandhya Sitasawad; Ramesh Bhonde (Natural Product Research, 2009)

Pseudomonas sp. strain AKM-P6 enhances tolerance of sorghum seedlings to elevated temperatures - Sk. Z. Ali; V. Sandhya; Minakshi Grover; N. Kishore; L. Venkateswar Rao; B. Venkateswarlu (Biology and Fertility of Soils, 2009)

Alleviation of drought stress effects in sunflower seedlings by the exopolysaccharides producing Pseudomonas putida strain GAP-P45 - V. Sandhya; Ali SK. Z.; Minakshi Grover; Gopal Reddy; B. Venkateswarlu (Biology and Fertility of Soils, 2009)

Predicting Inhibitors of Acetylcholinesterase by Regression and Classification Machine Learning Approaches with Combinations of Molecular Descriptors - Dmitriy Chekmarev; Vladyslav Kholodovych; Sandhya Kortagere; William J. Welsh; Sean Ekins (Pharmaceutical Research, 2009)

The Evolution of Guanylyl Cyclases as Multidomain Proteins: Conserved Features of Kinase-Cyclase Domain Fusions - Kabir Hassan Biswas; Avinash R. Shenoy; Anindya Dutta; Sandhya S. Visweswariah (Journal of Molecular Evolution, 2009)

Hybrid Scoring and Classification Approaches to Predict Human Pregnane X Receptor Activators - Sandhya Kortagere; Dmitriy Chekmarev; William J. Welsh; Sean Ekins (Pharmaceutical Research, 2009)

Gametogenic development and spawning of the mud clam, Polymesoda erosa (Solander, 1876) at Chorao Island, Goa - Sandhya Clemente; Baban Ingole (Marine Biology Research, 2009)

Biosequestering Potential of Spirulina platensis for Uranium - Arun Dheetcha; Sandhya Mishra (Current Microbiology, 2008)

New Predictive Models for Blood–Brain Barrier Permeability of Drug-like Molecules - Sandhya Kortagere; Dmitriy Chekmarev; William J. Welsh; Sean Ekins (Pharmaceutical Research, 2008)

Structural and functional characterization and physiological significance of a stimulator protein of Mg2+-independent Ca2+-ATPase isolated from goat spermatozoa - Tanusree Sengupta; Srabasti Ghoshal; Sandhya R. Dungdung; Gopal C. Majumder; Parimal C. Sen (Molecular and Cellular Biochemistry, 2008)

Hyperinsulinemia predisposes to NAFLD - Sandhya Mishra; Dharamveer Yadav; Monika Gupta; Hemant Mishra; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2008)

Impact of aerosols from the Asian Continent on the adjoining oceanic environments - K. Parameswaran; Sandhya K. Nair; K. Rajeev (Journal of Earth System Science, 2008)

Nuclear condensation and free radical scavenging: a dual mechanism of bisbenzimidazoles to modulate radiation damage to DNA - Urmila Tawar; Sandhya Bansal; Shiteshu Shrimal; Manish Singh; Vibha Tandon (Molecular and Cellular Biochemistry, 2007)

Type-2 diabetes related intermediate phenotypic traits in north Indian diabetics - S. K. Mathur; Piyush Chandra; Sandhya Mishra; Peeyush Ajmera; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2007)

Metabolic syndrome: Early identification prevents type II diabetes and cardiovascular disease - Praveen Sharma; Sandhya Mishra (Indian Journal of Clinical Biochemistry, 2007)

Formulation and evaluation of ketorolac tromethamine-loaded albumin microspheres for potential intramuscular administration - Sam T. Mathew; S. Gayathri Devi; KV Sandhya; KV Sandhya (AAPS PharmSciTech, 2007)

Comparison of genetic transformation in Morus alba L. via different regeneration systems - Sandhya Agarwal; Kamlesh Kanwar (Plant Cell Reports, 2007)

Lysophosphatidylcholine induces inflammatory activation of human coronary artery smooth muscle cells - Nambi Aiyar; Jyoti Disa; Zhaohui Ao; Haisong Ju; Sandhya Nerurkar; Robert N. Willette; Colin H. Macphee; Douglas G. Johns; Stephen A. Douglas (Molecular and Cellular Biochemistry, 2007)

ProRegIn: A regularity index for the selection of native-like tertiary structures of proteins - Lipi Thukral; Sandhya R Shenoy; Kumkum Bhushan; B Jayaram (Journal of Biosciences, 2007)

Development of sporeless/low sporing strains of Pleurotus through mutation - Sandhya Ravishankar; Meera Pandey; R. P. Tewari; V. Krishna (World Journal of Microbiology and Biotechnology, 2006)

Image representation, scaling and cognitive model of object perception - Sandeep Kumar Ganji; Indu Potula; Venkata Naga Pradeep Ambati; Bhujanga Rao; Sandhya Kumari Ganji; Shwetha Kumari Ganji (Cognitive Processing, 2006)

Oxidative stress, α-tocopherol, ascorbic acid and reduced glutathione status in schizophrenics - Gora Dadheech; Sandhya Mishra; Shiv Gautam; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2006)

Serum calcium measurement: Total versus free (ionized) calcium - Laxmayya Sava; Sandhya Pillai; Umesh More; Alka Sontakke (Indian Journal of Clinical Biochemistry, 2005)

Oxidative stress in metabolic syndrome - Praveen Sharma; Sandhya Mishra; Peeyush Ajmera; Sandeep Mathur (Indian Journal of Clinical Biochemistry, 2005)

Antioxidant status and peroxidative stress in mother and newborn —A pilot study - Chitra Upadhyaya; Sandhya Mishra; P. P. Singh; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2005)

Reduced glutathione: Importance of specimen collection - Sarita Chavan; Laxmayya Sava; Vishal Saxena; Sandhya Pillai; Alka Sontakke; Digamber Ingole (Indian Journal of Clinical Biochemistry, 2005)

Serum iron, copper and zinc status in maternal and cord blood - Chitra Upadhyaya; Sandhya Mishra; Peeyush Ajmera; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2004)

Studies of biochemical parameters in breast cancer with and without metastasis - Sandhya Mishra; D. C. Sharma; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2004)

Evaluation of the effect of lipoic acid administered along with gentamicin in rats rendered bacteremic - Palaninathan Varalakshmi; Sunil Sandhya; Kumaravel Palanichamy Malarkodi (Molecular and Cellular Biochemistry, 2003)

Effect of Sub-Lethal Concentrations of Endosulfan on Hematological and Serum Biochemical Parameters in the Carp Cyprinus carpio - F. Jenkins; J. Smith; B. Rajanna; U. Shameem; K. Umadevi; V. Sandhya; R. Madhavi (Bulletin of Environmental Contamination and Toxicology, 2003)

A Human Vaccine Strain of Lamb Rotavirus (Chinese) NSP4 Gene: Complete Nucleotide Sequence and Phylogenetic Analyses - Ketha V. Krishna Mohan; Sandhya Kulkarni; Roger I. Glass; Bai ZhiSheng; Chintamani D. Atreya (Virus Genes, 2003)

Reflection ofP andSV waves at the free surface of a monoclinic elastic half-space - Sarva Jit Singh; Sandhya Khurana (Journal of Earth System Science, 2002)

The ascent of nucleotide cyclases: conservation and evolution of a theme - Avinash R. Shenoy; N. Srinivasan; Sandhya S. Visweswariah (Journal of Biosciences, 2002)

Forest change detection in Kalarani round, Vadodara, Gujarat— a Remote Sensing and GIS approach - Jessica P Karia; M C Porwal; P S Roy; G Sandhya (Journal of the Indian Society of Remote Sensing, 2001)

Forestry for sustainable biomass production and carbon sequesteration in India - N.H. Ravindranath; P. Sudha; Sandhya Rao (Mitigation and Adaptation Strategies for Global Change, 2001)

Tyrosine phosphorylation of the human guanylyl cyclase C receptor - Rashna Bhandari; Roy Mathew; K. Vijayachandra; Sandhya S. Visweswariah (Journal of Biosciences, 2000)

Effects of antiprogestins on the rate of proliferation of breast cancer cells - Kazumi Iwasaki; Bill Underwood; Michelle Herman; Sumi Dinda; Sandhya Kodali; H.J. Kloosterboer; Cliff Hurd; V.K. Moudgil (Molecular and Cellular Biochemistry, 1999)

Pharmacodynamics and Toxicodynamics of Drug Action: Signaling in Cell Survival and Cell Death - Ah-Ng Tony Kong; Sandhya Mandlekar; Rong Yu; Wei Lei; Adedigbo Fasanmande (Pharmaceutical Research, 1999)

Elucidation of the lesions present in the transcription defectivefitA76 mutant ofEscherichia coli: Implication of phenylalanyl tRNA synthetase subunits as transcription factors - Sandhya Ramalingam; M. Hussain Munavar; S. Sudha; A. Ruckmani; R. Jayaraman (Journal of Biosciences, 1999)

Expression of hup Genes in Azorhizobium caulinodans and Their Coregulation With RuBP Carboxylase - Sandhya Sanghi; M. L. Lodha (Journal of Plant Biochemistry and Biotechnology, 1998)

Inhibition of proliferation of T47D human breast cancer cells: Alterations in progesterone receptor and p53 tumor suppressor protein - Sumi Dinda; Sandhya Kodali-Gali; Lisa Sevilla; Michael Burkley; Cliff Hurd; V.K. Moudgil (Molecular and Cellular Biochemistry, 1997)

Solid phase synthesis of combinatorial libraries using anhydrides as templates - John Perumattam; Sarvajit Chakravarty; Glenn A. McEnroe; R. Richard Goehring; Babu Mavunkel; Sandhya Suravajjala; Whitney W. Smith; Baili Chen (Molecular Diversity, 1997)

Regulation of cellular signals by G-proteins - K. Sandhya; Mohan C. Vemuri (Journal of Biosciences, 1997)

Purification and regulation of glutamine synthetase in a collagenolytic Vibrio alginolyticus strain - Sandhya J. Bodasing; Paul W. Brandt; Frank T. Robb; David R. Woods (Archives of Microbiology, 1985)